Method for producing dry powder of cellulose fiber
A method for producing a dry powder of cellulose fibers through slurry preparation and granulation under reduced pressure addresses the redispersibility and storage issues, achieving efficient composite formation with resins.
Patent Information
- Application Number
- JP2020181652
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-06-30
- Filing Date
- 2020-10-29
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-10-29
AI Technical Summary
Cellulose nanofibers, when dried from a dispersion state, lose their good dispersion properties and are difficult to redisperse effectively, and their storage and transportation are hindered by moisture and volume issues.
A method involving slurry preparation and granulation under reduced pressure to produce a dry powder of cellulose fibers, using specific drying conditions and additives to maintain redispersibility.
The method produces a dry powder of cellulose fibers with excellent redispersibility, enabling efficient composite formation with resins, reducing storage and transportation costs, and maintaining mechanical properties.
Smart Images

Figure 0007662323000003 
Figure 0007662323000004 
Figure 0007662323000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a dry powder of cellulose fibers, and a method for producing a composite containing cellulose fibers and a resin (also referred to as a resin composite in the present disclosure). [Background technology]
[0002] Thermoplastic resins are light and have excellent processability, and therefore are widely used in many fields such as automobile parts, electrical and electronic parts, office equipment housings, and precision parts. However, resins alone often have insufficient mechanical properties and dimensional stability, and therefore composites of resins and various fillers are generally used. In recent years, the use of nanofibers such as cellulose nanofibers (CNF) as such fillers has been considered. Nanofibers such as CNF have the property of easily agglomerating in a dry state, so they are produced as a dispersion liquid that allows stable dispersion. When applying cellulose nanofibers to various applications, the above dispersion liquid may be dried and then redispersed in a dispersion medium to prepare a redispersion liquid.
[0003] Patent Document 1 describes a method for redispersing a cellulose nanofiber dispersion by drying a produced cellulose nanofiber dispersion and dispersing the cellulose nanofiber powder particles produced in an aqueous solvent again, which is characterized in that when the cellulose nanofiber powder particles are redispersed in the aqueous solvent, they are stirred and mechanical shear force is applied.
[0004] Patent document 2 describes a method for treating chemically modified fibril cellulose, which comprises introducing the chemically modified fibril cellulose material into a thermal drying device (20) comprising a belt (22) so that the fibril cellulose material forms at least one rod-shaped body on the belt (22), and dewatering the chemically modified fibril cellulose material on the belt (22) using a heated air flow having a temperature of at least 40°C, concentrating and / or drying the chemically modified fibril cellulose material such that the dry solids content of the fibril cellulose material after the thermal drying device (20) is at least 10%.
[0005] Patent Document 3 describes powdered nanofibers, which are characterized in that (A) powdered nanofibers are mixed with (B) a dispersant in an amount of 1 to 40% by weight, calculated as solid content, and have a bulk density of 90 to 200 g / L.
[0006] Patent Document 4 describes a method in which cellulose nanofibers are homogenized in the presence of an organic solvent, and then the organic solvent is removed to produce dry microfibers with a moisture content of 0 to 1% by mass. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] International Publication No. 2017 / 154568 [Patent Document 2] Special Publication No. 2015-512964 [Patent Document 3] JP 2017-210596 A [Patent Document 4] JP 2012-224960 A Summary of the Invention [Problem to be solved by the invention]
[0008] When cellulose fibers, particularly cellulose nanofibers, are stored or transported in the form of a dispersion, problems arise in that the cellulose fibers are easily deteriorated (putrefaction, etc.) because they are placed in a humid environment, and that the dispersion medium occupies extra volume and weight, increasing storage and transportation costs. If the cellulose fibers are stored or transported in a dry state, the volume and weight can be reduced, and there is also the advantage that it is easy to composite with other materials depending on the application. However, once the cellulose fibers are dried from the dispersion state, it is difficult to reproduce the good dispersion state of the cellulose fibers before drying (i.e., to obtain good redispersibility) even if they are subsequently redispersed in a dispersion medium.
[0009] The present invention aims to solve the above-mentioned problems and provide a method for producing a dry powder of cellulose fibers that exhibits good redispersibility, and a method for producing a resin composite that includes using the dry powder prepared by the method. [Means for solving the problem]
[0010] As a result of intensive research to solve the above problems, the present inventors have found that when a dry powder of cellulose fibers is produced under specific drying conditions, a dry powder of cellulose fibers having excellent redispersibility can be produced, and have thus completed the present invention. That is, the present invention encompasses the following aspects.
[0011] [1] A method for producing a dry powder of cellulose fibers, comprising: A slurry preparation step of preparing a slurry containing cellulose fibers and water; and a granulation step of agitating the slurry under reduced pressure to form a dry powder of the cellulose fibers; Including, The method, wherein the granulating step comprises forming particles of the cellulose fibers by the agitation and chopping the particles. [2] The method according to claim 1, wherein the slurry contains at least 5% by weight of water at the start of the granulation step. [3] The method according to any one of the preceding claims, wherein an additional medium, which is a liquid medium other than water, is added to the slurry in the granulation step. [4] The method of claim 3, wherein the granulation step comprises adding an additional medium, which is a liquid medium other than water, to the slurry in two or more portions. [5] The method according to claim 3 or 4, wherein the additional medium is selected from the group consisting of alcohols having a boiling point of 50° C. to 170° C.; ethers; carboxylic acids; esters; ketones; and nitrogen-containing solvents. [6] The method according to any one of Aspects 3 to 5 above, wherein the additional medium is a substance that forms an azeotrope with water. [7] The method of claim 6, wherein the additional medium is added to the slurry in a proportion higher than the azeotropic composition ratio with water. [8] The method according to any one of the above aspects 3 to 7, wherein the additional medium is added to the slurry in a mass ratio of water:additional medium in the slurry in the range of 1:99 to 90:10. [9] A method for producing a dry powder of cellulose fibers, comprising: A slurry preparation step of preparing a slurry comprising cellulose fibers and a liquid medium; and a granulation step of agitating the slurry under reduced pressure to form a dry powder of the cellulose fibers; Including, The method, wherein the granulating step comprises forming particles of the cellulose fibers by the agitation and chopping the particles.
[10] The method according to aspect 9, wherein the liquid medium is at least one selected from the group consisting of alcohols, ethers, carboxylic acids, esters, ketones, and nitrogen-containing solvents, all having a boiling point of 50°C to 170°C.
[11] The method according to any one of the above aspects 1 to 10, wherein a binder is added to the slurry in the slurry preparation step and / or the granulation step.
[12] The method of claim 11, wherein the binder is selected from the group consisting of polyalkylene oxides, cellulose ethers, and cellulose esters.
[13] The method according to aspect 11 or 12, wherein in the slurry preparation step and / or the granulation step, the binder is dissolved in a medium and added to the slurry.
[14] The granulation step is carried out in a granulator equipped with an agitator blade, a chopper blade, and a pressure reduction mechanism; In the granulation step, the stirring is performed by rotating the stirring blade at a peripheral speed of 0.5 m / sec to 40 m / sec, and the chopper pulverization is performed by rotating the chopper blade at a speed of 100 rpm to 6000 rpm. 14. The method according to any one of the above-mentioned aspects 1 to 13, wherein the granulator is configured so that the chopper-pulverized particles are further subjected to the stirring.
[15] The granulation step is carried out in a granulator equipped with an agitator blade, a chopper blade, and a pressure reduction mechanism; In the granulation step, the stirring is performed by rotating the stirring blade at a peripheral speed of 0.5 m / sec to 40 m / sec, and the chopper pulverization is performed by rotating the chopper blade at a peripheral speed of 0.5 m / sec to 40 m / sec, 15. The method according to any one of the above-mentioned aspects 1 to 14, wherein the granulator is configured so that the chopper-pulverized particles are further subjected to the stirring.
[16] The method according to claim 15, wherein the peripheral speed of the chopper blade is equal to or lower than the peripheral speed of the agitating blade.
[17] The method according to any one of the above-mentioned aspects 1 to 16, wherein the granulation step is carried out at a temperature of 20 to 160° C. and at a reduced pressure of −100 kPa to −1 kPa.
[18] The method according to any one of aspects 1 to 17, wherein the bulk density of the dry powder is 0.05 g / mL to 1.0 g / mL.
[19] The method according to any one of aspects 1 to 18, wherein cellulose fibers derived from cotton linters are used.
[20] The method according to any one of aspects 1 to 19, wherein chemically modified cellulose fibers are used.
[21] The method according to any one of the above aspects 1 to 20, wherein cellulose fibers are chemically modified with a hydrophobic substituent.
[22] The method according to any one of the above aspects 1 to 21, wherein the cellulose fibers have a number average fiber diameter of 10 nm or more and 1,000 nm or less.
[23] A method for producing a composite containing cellulose fibers and a resin, the method comprising: preparing a dry powder by the method described in any one of Aspects 1 to 22 above; and mixing the dry powder with the resin.
[24] The resin is a thermoplastic resin, 24. The method of claim 23, wherein the dry powder and the resin are mixed by melt kneading. Effect of the Invention
[0012] According to one aspect of the present invention, there can be provided a method for producing a dry powder of cellulose fibers exhibiting good redispersibility, and a method for producing a resin composite including using the dry powder prepared by the method. [Brief description of the drawings]
[0013] [Figure 1] 11 is an explanatory diagram of a method for calculating the IR index 1370 and the IR index 1030. FIG. [Diagram 2] FIG. 2 is an explanatory diagram of a method for measuring the thermal decomposition onset temperature (TD) and the 1% weight loss temperature (T1%). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Exemplary embodiments of the present invention will be described in detail below, but the present invention is not limited to these embodiments.
[0015] <Method for producing dry powder of cellulose fiber> One aspect of the present invention provides a method for producing a dry powder of cellulose fibers, comprising: a slurry preparation step of preparing a dispersion (slurry) containing cellulose fibers and a liquid medium (in one aspect, a liquid medium containing water); and a granulation step of stirring the slurry under reduced pressure to form a dry powder of the cellulose fibers, the granulation step including forming particles of the cellulose fibers by stirring and chopping the particles.
[0016] <Slurry preparation process> In this step, a slurry containing cellulose fibers and a liquid medium (in one embodiment, a liquid medium containing water) is prepared. As the raw material of the cellulose fibers, natural cellulose and regenerated cellulose can be used. As the natural cellulose, wood pulp obtained from wood species (broadleaf or coniferous trees), non-wood pulp obtained from non-wood species (cotton, bamboo, hemp, bagasse, kenaf, cotton linters, sisal, straw, etc.), and cellulose fiber aggregates produced by animals (e.g., ascidians), algae, and microorganisms (e.g., acetic acid bacteria) can be used. As the regenerated cellulose, regenerated cellulose fibers (viscose, cupra, tencel, etc.), cellulose derivative fibers, and ultrafine threads of regenerated cellulose or cellulose derivatives obtained by the electrospinning method can be used. Non-wood pulp obtained from cotton linters is preferable in that it can obtain cellulose fibers with high purity and high crystallinity.
[0017] In one embodiment, the cellulose fiber is a cellulose nanofiber. The cellulose nanofiber refers to fine cellulose obtained by treating pulp or the like with hot water of 100°C or higher to hydrolyze and weaken the hemicellulose, and then defibrating the cellulose by a pulverizing method using a high-pressure homogenizer, a microfluidizer, a ball mill, a disk mill, a mixer (e.g., a homomixer), or the like. In one embodiment, the cellulose nanofiber has a number average fiber diameter of 1 nm or more and 1000 nm or less. The cellulose fiber may be chemically modified as described below.
[0018] The slurry can be prepared by dispersing cellulose fibers (e.g., cellulose nanofibers obtained through the above-mentioned defibration) in a liquid medium, and the dispersion can be performed using a high-pressure homogenizer, a microfluidizer, a ball mill, a disk mill, a mixer (e.g., a homomixer), or the like. For example, the product of the above-mentioned defibration can be obtained as the product of the slurry preparation step of the present disclosure. In one embodiment, the liquid medium in the slurry can contain water, and in another embodiment, can be free of water. In one embodiment, the liquid medium can contain water and, optionally, other liquid media (e.g., organic solvents) either alone or in combination of two or more. Examples of the organic solvent include commonly used water-miscible organic solvents having a boiling point of 50°C to 170°C, such as alcohols (e.g., methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, s-butanol, t-butanol, etc.); ethers (e.g., propylene glycol monomethyl ether, 1,2-dimethoxyethane, diisopropyl ether, tetrahydrofuran, 1,4-dioxane, etc.); carboxylic acids (e.g., formic acid, acetic acid, lactic acid, etc.); esters (e.g., ethyl acetate, vinyl acetate, etc.); ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, etc.); and nitrogen-containing solvents (dimethylformamide, dimethylacetamide, acetonitrile, etc.). It is preferable that these organic solvents are substances that form an azeotropic mixture with water. In particular, it is more preferable that the organic solvent has a minimum azeotropic point, which is the boiling point of the azeotropic mixture that is lower than the boiling points of water and the organic solvent alone, because it is easy to dry off water even at a low vacuum and / or temperature. In a typical embodiment, the liquid medium in the slurry is substantially only water.
[0019] When the liquid medium does not contain water, the liquid medium may be a water-miscible organic solvent commonly used, such as: alcohols (e.g., methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, s-butanol, t-butanol, etc.) having a boiling point of 50° C. to 170° C.; ethers (e.g., propylene glycol monomethyl ether, 1,2-dimethoxyethane, diisopropyl ether, tetrahydrofuran, 1,4-dioxane, etc.); carboxylic acids (e.g., formic acid, acetic acid, lactic acid, etc.); esters (e.g., ethyl acetate, etc.); The solvent may be one or more selected from the group consisting of: solvents (e.g., ethyl, vinyl acetate, etc.); ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, etc.); nitrogen-containing solvents (dimethylformamide, dimethylacetamide, acetonitrile, etc.) and hydrophobic organic solvents, such as aromatic hydrocarbons (benzene, toluene, xylene, etc.); aliphatic hydrocarbons (hexane, heptane, octane, decane, etc.); halogenated hydrocarbons (tetrachloromethane, chloroform, dichloromethane, chloroethane, etc.), etc.
[0020] In addition to the cellulose fibers and the liquid medium, the slurry may contain additives (binders, dispersants, antioxidants, preservatives, thickeners, etc.).
[0021] Since the cellulose raw material contains alkali soluble matter and sulfuric acid insoluble matter (lignin, etc.), the alkali soluble matter and sulfuric acid insoluble matter may be reduced through a refining process such as delignification by cooking and a bleaching process. On the other hand, the refining process such as delignification by cooking and the bleaching process cut the molecular chains of cellulose, changing the weight average molecular weight and number average molecular weight, so it is desirable that the refining process and the bleaching process of the cellulose raw material control the weight average molecular weight of cellulose and the ratio of the weight average molecular weight to the number average molecular weight so as not to deviate from an appropriate range.
[0022] In addition, since the refining process such as delignification by cooking and the bleaching process reduce the molecular weight of cellulose molecules, there is a concern that these processes will result in a lower molecular weight of cellulose and an increase in the proportion of alkali-soluble matter present due to the alteration of the cellulose raw material. Since alkali-soluble matter has poor heat resistance, it is desirable to control the refining process and bleaching process of the cellulose raw material so that the amount of alkali-soluble matter contained in the cellulose raw material is within a certain range or less.
[0023] In one embodiment, the number average fiber diameter (D) of the cellulose fibers is preferably 2 to 1000 nm from the viewpoint of obtaining a good effect of improving physical properties by the cellulose fibers. The number average fiber diameter of the cellulose fibers is more preferably 4 nm or more, or 5 nm or more, or 10 nm or more, or 15 nm or more, or 20 nm or more, and more preferably 500 nm or less, or 450 nm or less, or 400 nm or less, or 350 nm or less, or 300 nm or less, or 250 nm or less.
[0024] In one embodiment, the number average fiber length (L) of the cellulose fibers is preferably 100 nm to 1000 μm from the viewpoint of obtaining a good effect of improving physical properties by the cellulose fibers. The number average fiber length of the cellulose fibers is more preferably 200 nm or more, or 500 nm or more, or 1 μm or more, or 10 μm or more, or 100 μm or more, and more preferably 500 μm or less, or 300 μm or less, or 200 μm or less.
[0025] From the viewpoint of satisfactorily improving the mechanical properties of a resin composite containing cellulose fibers with a small amount of cellulose fibers, the average L / D of the cellulose fibers is preferably 50 or more, or 80 or more, or 100 or more, or 120 or more, or 150 or more. There is no particular upper limit, but from the viewpoint of handleability, it is preferably 5,000 or less.
[0026] In one embodiment, the number average fiber diameter (D), number average fiber length (L), and L / D ratio of the cellulose fibers of the present disclosure are values measured by the following procedure using a scanning electron microscope (SEM). The aqueous dispersion of cellulose fibers is replaced with t-butanol, diluted to 0.001 to 0.1 mass%, and dispersed using a high-shear homogenizer (e.g., IKA, product name "Ultra Turrax T18") under processing conditions: rotation speed 15,000 rpm x 3 minutes, cast on an osmium-deposited silicon substrate, and air-dried to obtain a measurement sample, which is measured using a high-resolution scanning electron microscope (SEM). Specifically, the length (L) and diameter (D) of 100 randomly selected fibrous substances are measured in an observation field where the magnification is adjusted so that at least 100 fibrous substances are observed, and the ratio (L / D) is calculated. The number average value of the length (L), the number average value of the diameter (D), and the number average value of the ratio (L / D) of the cellulose fibers are calculated.
[0027] In another embodiment, the number average fiber diameter of the cellulose fiber of the present disclosure is a number average fiber diameter calculated from a specific surface area obtained by the BET method using nitrogen adsorption. 2 / g or higher.
[0028] The method for calculating the number-average fiber diameter by nitrogen adsorption is as follows. That is, an aqueous dispersion of cellulose fibers is replaced with t-butanol, and then the dispersion is filtered, concentrated, and dried to produce a porous sheet, and the specific surface area of the porous sheet is measured using the BET method by nitrogen adsorption. The cellulose is measured in an ideal state where no fusion between fibers occurs and the cellulose density is d (g / cm 3 ) and a cylindrical fiber with a diameter D (nm), the relationship between the specific surface area and the fiber diameter is expressed by the following formula. Specific surface area (m 2 / g)=4000 / (dD) And the cellulose density is 1.50 g / cm 3 Then, the number average fiber diameter is expressed by the following formula: D(nm)=2667 / specific surface area(m 2 / g) Therefore, when D is 1000 nm, the specific surface area is 2.667 m 2 / g.
[0029] The length, diameter, and L / D ratio of the cellulose fibers in the resin composite described below are measured by dissolving the resin components in the resin composite in an organic or inorganic solvent capable of dissolving the resin components of the resin composite, separating the cellulose fibers, thoroughly washing the cellulose fibers with the solvent, and then replacing the resulting mixture with t-butanol to prepare a 0.001 to 0.1 mass% dispersion. The resulting dispersion is then redispersed using a high-shear homogenizer (e.g., IKA product, trade name "Ultra-Turrax T18").
[0030] The crystallinity of the cellulose fibers is preferably 55% or more. When the crystallinity is in this range, the mechanical properties (strength, dimensional stability) of the cellulose fibers themselves are high, and therefore when the cellulose fibers are dispersed in a resin, the strength and dimensional stability of the resin composite tend to be high. A more preferable lower limit of the crystallinity is 60%, even more preferably 70%, and most preferably 80%. There is no particular upper limit for the crystallinity of the cellulose fibers, and the higher the better, but from the viewpoint of production, a preferable upper limit is 99%.
[0031] Alkali-soluble polysaccharides such as hemicellulose and acid-insoluble components such as lignin are present between the microfibrils and between the microfibril bundles of plant-derived cellulose. Hemicellulose is a polysaccharide composed of sugars such as mannan and xylan, and plays a role in binding the microfibrils together by hydrogen bonding with cellulose. Lignin is a compound having an aromatic ring, and is known to be covalently bonded to hemicellulose in the cell walls of plants. If there is a large amount of impurities such as lignin remaining in the cellulose fibers, discoloration may occur due to heat during processing. Therefore, from the viewpoint of suppressing discoloration of the resin composite during extrusion processing and molding processing, it is desirable to set the crystallinity of the cellulose fibers within the above-mentioned range.
[0032] The degree of crystallinity here, when the cellulose fiber is cellulose type I crystal (derived from natural cellulose), is calculated from the diffraction pattern (2θ / deg. is 10 to 30) obtained by measuring the sample by wide-angle X-ray diffraction, using the Segal method and the following formula. Crystallinity (%) = ([diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] - [diffraction intensity due to amorphous matter at 2θ / deg. = 18]) / [diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] × 100
[0033] When the cellulose fiber is a cellulose II type crystal (derived from regenerated cellulose), the degree of crystallinity can be calculated from the absolute peak intensity h0 at 2θ=12.6° assigned to the (110) plane peak of the cellulose II type crystal in wide-angle X-ray diffraction and the peak intensity h1 from the baseline at this interplanar spacing, according to the following formula: Crystallinity (%) =h1 / h0 ×100 As the measurement sample, the above-mentioned porous sheet is used.
[0034] Known crystalline forms of cellulose include type I, type II, type III, and type IV, among which types I and II are particularly widely used, and types III and IV are obtained on a laboratory scale but are not widely used on an industrial scale. The cellulose fibers of the present disclosure are preferably cellulose fibers containing cellulose type I crystals or cellulose type II crystals, since they have relatively high structural mobility and, by dispersing the cellulose fibers in a resin, a resin composite having a lower linear expansion coefficient and superior strength and elongation during tensile and bending deformation can be obtained, and more preferably cellulose fibers containing cellulose type I crystals and having a crystallinity of 55% or more.
[0035] In addition, the degree of polymerization of the cellulose fibers is preferably 100 or more, more preferably 150 or more, more preferably 200 or more, more preferably 300 or more, more preferably 400 or more, more preferably 450 or more, and preferably 3500 or less, more preferably 3300 or less, more preferably 3200 or less, more preferably 3100 or less, and more preferably 3000 or less.
[0036] From the viewpoint of processability and mechanical property expression, it is desirable that the polymerization degree of the cellulose fiber is within the above-mentioned range. From the viewpoint of processability, it is preferable that the polymerization degree is not too high, and from the viewpoint of mechanical property expression, it is desirable that the polymerization degree is not too low.
[0037] The degree of polymerization of cellulose fibers means the average degree of polymerization measured according to the reduced specific viscosity method using a copper ethylenediamine solution described in the Verification Test (3) of the "15th Revised Japanese Pharmacopoeia Commentary (published by Hirokawa Shoten)."
[0038] In one embodiment, the weight average molecular weight (Mw) of the cellulose fiber is 100,000 or more, more preferably 200,000 or more. The ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) is 6 or less, preferably 5.4 or less. The larger the weight average molecular weight, the fewer the number of terminal groups of the cellulose molecule. In addition, since the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight represents the width of the molecular weight distribution, the smaller the Mw / Mn, the fewer the number of terminals of the cellulose molecule. Since the terminals of the cellulose molecule are the starting points of thermal decomposition, when the cellulose molecule of the cellulose fiber not only has a large weight average molecular weight but also has a narrow molecular weight distribution width, a particularly high heat resistant cellulose fiber and a resin composite containing the cellulose fiber and a resin can be obtained. The weight average molecular weight (Mw) of the cellulose fiber may be, for example, 600,000 or less, or 500,000 or less, from the viewpoint of the availability of the cellulose raw material. From the viewpoint of ease of production of cellulose fibers, the ratio (Mw / Mn) of weight average molecular weight to number average molecular weight (Mn) may be, for example, 1.5 or more, or 2 or more. Mw can be controlled within the above range by selecting a cellulose raw material having an Mw appropriate for the purpose, appropriately subjecting the cellulose raw material to physical treatment and / or chemical treatment within an appropriate range, etc. Mw / Mn can also be controlled within the above range by selecting a cellulose raw material having an Mw / Mn appropriate for the purpose, appropriately subjecting the cellulose raw material to physical treatment and / or chemical treatment within an appropriate range, etc. In both the control of Mw and the control of Mw / Mn, examples of the physical treatment include dry or wet grinding using a microfluidizer, ball mill, disk mill, or the like, and physical treatments that apply mechanical forces such as impact, shear, friction, and the like using a crusher, homomixer, high-pressure homogenizer, ultrasonic device, or the like, and examples of the chemical treatment include digestion, bleaching, acid treatment, and conversion to regenerated cellulose.
[0039] The weight average molecular weight and number average molecular weight of cellulose referred to here are values determined by dissolving cellulose in N,N-dimethylacetamide containing added lithium chloride and then subjecting the cellulose to gel permeation chromatography using N,N-dimethylacetamide as a solvent.
[0040] Methods for controlling the degree of polymerization (i.e., average degree of polymerization) or molecular weight of cellulose fibers include hydrolysis. The hydrolysis promotes depolymerization of amorphous cellulose inside the cellulose fibers, decreasing the average degree of polymerization. At the same time, the hydrolysis removes impurities such as hemicellulose and lignin in addition to the amorphous cellulose, making the inside of the fibers more porous.
[0041] The hydrolysis method is not particularly limited, and examples thereof include acid hydrolysis, alkali hydrolysis, hydrothermal decomposition, steam explosion, and microwave decomposition. These methods may be used alone or in combination of two or more. In the acid hydrolysis method, for example, α-cellulose obtained as pulp from a fibrous plant is used as a cellulose raw material, and this is dispersed in an aqueous medium, and an appropriate amount of protonic acid, carboxylic acid, Lewis acid, heteropolyacid, etc. is added, and the mixture is heated while stirring, so that the average degree of polymerization can be easily controlled. The reaction conditions such as temperature, pressure, and time at this time vary depending on the cellulose type, cellulose concentration, acid type, acid concentration, etc., but are appropriately adjusted so that the desired average degree of polymerization is achieved. For example, a condition in which cellulose is treated for 10 minutes or more at 100°C or higher under pressure using an aqueous mineral acid solution of 2% by mass or less can be exemplified. Under these conditions, the catalyst component such as acid penetrates into the inside of the cellulose fiber, promoting hydrolysis, reducing the amount of catalyst component used, and making subsequent purification easier. The dispersion of the cellulose raw material during hydrolysis may contain, in addition to water, a small amount of an organic solvent within a range that does not impair the effects of the present invention.
[0042] Alkali-soluble polysaccharides that may be contained in cellulose fibers include hemicellulose, β-cellulose, and γ-cellulose. Alkali-soluble polysaccharides are understood by those skilled in the art as components obtained as the alkali-soluble portion of holocellulose obtained by solvent extraction and chlorine treatment of plants (e.g., wood) (i.e., components obtained by removing α-cellulose from holocellulose). Alkali-soluble polysaccharides are polysaccharides containing hydroxyl groups and have poor heat resistance, and may cause inconveniences such as decomposition when exposed to heat, yellowing during heat aging, and a decrease in the strength of cellulose fibers. Therefore, it is preferable that the content of alkali-soluble polysaccharides in cellulose fibers is low.
[0043] In one embodiment, the average content of alkali-soluble polysaccharides in the cellulose fibers is preferably 20% by mass or less, 18% by mass or less, 15% by mass or less, or 12% by mass or less, based on 100% by mass of the cellulose fibers, from the viewpoint of obtaining good dispersibility of the cellulose fibers. From the viewpoint of ease of production of the cellulose fibers, the content may be 1% by mass or more, 2% by mass or more, or 3% by mass or more.
[0044] The average alkali-soluble polysaccharide content can be determined by the method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000), by subtracting the α-cellulose content from the holocellulose content (Wise method). This method is understood in the industry as a method for measuring the amount of hemicellulose. The alkali-soluble polysaccharide content is calculated three times for each sample, and the number average of the calculated alkali-soluble polysaccharide contents is taken as the average alkali-soluble polysaccharide content.
[0045] In one embodiment, the average content of acid-insoluble components in the cellulose fibers is preferably 10% by mass or less, 5% by mass or less, or 3% by mass or less, based on 100% by mass of the cellulose fibers, from the viewpoint of avoiding a decrease in heat resistance of the cellulose fibers and the associated discoloration. From the viewpoint of ease of production of the cellulose fibers, the content may be 0.1% by mass or more, 0.2% by mass or more, or 0.3% by mass or more.
[0046] The average acid-insoluble content is determined as a quantitative determination of the acid-insoluble content using the Clason method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000). This method is understood in the industry as a method for measuring the amount of lignin. The sample is stirred in a sulfuric acid solution to dissolve cellulose, hemicellulose, etc., and then filtered through a glass fiber filter paper, and the resulting residue corresponds to the acid-insoluble content. The acid-insoluble content is calculated from the weight of the acid-insoluble content, and the number average of the acid-insoluble content calculated for the three samples is taken as the average acid-insoluble content.
[0047] The thermal decomposition temperature of cellulose fibers (T D ) is 270° C. or higher in one embodiment, from the viewpoint of exhibiting heat resistance and mechanical strength desired for in-vehicle applications and the like, preferably 275° C. or higher, more preferably 280° C. or higher, and even more preferably 285° C. or higher. The higher the thermal decomposition onset temperature, the more preferable it is, but from the viewpoint of ease of production of cellulose fibers, it may be, for example, 320° C. or lower, or 300° C. or lower.
[0048] In this disclosure, T D As shown in the explanatory diagram of Figure 2, this is a value obtained from a graph in which the horizontal axis is temperature and the vertical axis is the weight residual rate % in a thermogravimetric (TG) analysis (note that Figure 2(B) is an enlarged view of Figure 2(A)). Starting from the weight of cellulose fiber at 150°C (a state in which most of the moisture has been removed) (weight loss of 0 wt%), the temperature was continued to be increased until the temperature at which the weight loss reached 1 wt% (T 1% ) and the temperature at which the weight loss reaches 2 wt% (T 2% The temperature at the point where this line intersects with the horizontal line (baseline) that passes through the starting point of the weight loss of 0 wt% is called T D It is defined as:
[0049] 1% weight loss temperature (T 1% ) is the above T D This is the temperature at which the weight loss reaches 1% by weight, starting from the weight at 150°C, when the temperature is continued to be increased using the method described above.
[0050] Weight loss rate of cellulose fiber at 250℃ (T 250℃ ) is the weight loss rate when cellulose fiber is kept at 250°C under nitrogen flow for 2 hours in TG analysis.
[0051] The concentration of cellulose fibers in the slurry to be subjected to the process of the present invention is preferably 5% by mass or more, or 10% by mass or more, or 15% by mass or more, or 20% by mass or more, or 25% by mass or more from the viewpoint of process efficiency in the subsequent granulation process, and is preferably 60% by mass or less, or 55% by mass or less, or 50% by mass or less, or 45% by mass or less from the viewpoint of maintaining good handleability by avoiding an excessive increase in the viscosity of the slurry and solidification due to aggregation. Generally, cellulose nanofibers are often produced in a dilute dispersion, and the cellulose concentration in the slurry may be adjusted to the above-mentioned preferred range by concentrating such a dilute dispersion. For concentration, methods such as suction filtration, pressure filtration, centrifugal deliquation, and heating can be used.
[0052] <Granulation process> In this step, the slurry obtained in the slurry preparation step is stirred under reduced pressure to form a dry powder of cellulose fibers. The granulation step can be carried out, for example, using a high-speed stirring granulator equipped with a stirring blade, a chopper blade, and a pressure reduction mechanism, and includes forming cellulose fiber particles by stirring and crushing the particles with a chopper.
[0053] The stirring blade and the chopper blade may have different or the same rotation axis.
[0054] A granulator having a rotating shaft on which the stirring blade and chopper blade are disposed on different axes may be equipped, for example, with a vertical or horizontal can body having a material inlet at the top, a combination of a slow-rotating stirring blade disposed at the bottom of the can body and a fast-rotating chopper blade disposed on the side of the can body, a pressure reducing mechanism, and optionally a temperature adjustment mechanism.
[0055] A granulator in which the stirring blade and chopper blade share the same rotating shaft may be equipped, for example, with a vertical or horizontal can body having a material inlet at the top, a combination of a stirring blade arranged at the bottom of the can body and a chopper blade arranged above the same rotating shaft, a pressure reducing mechanism, and optionally a temperature control mechanism. When the measured amount of slurry is fed into the can through the material supply port, the slurry is dried under reduced pressure while convecting inside the can due to the centrifugal force and upward propulsion force of the stirring blade, producing particles. The particles move inside the can and are crushed by hitting the chopper blade, which has a strong shearing force, and then return to the vicinity of the stirring blade and are stirred again to increase the particle size. In this way, the particles are repeatedly subjected to stirring and chopper crushing, thereby producing a dry powder of cellulose fibers with a regular size (i.e., with small variation in particle size).
[0056] The stirring blade may be a rotor having two blades, three blades, four blades, etc., or may be a rotor in which a plurality of blades are connected in a ring shape and integrated. The rotor may also have a multi-stage structure with upper and lower blades. The blade surface of the rotor may be perpendicular or inclined to the rotation axis, and may be flat or curved, or a combination of these. From the viewpoint of obtaining good stirring efficiency, the rotor is preferably arranged so as to follow the bottom surface and side wall of the can body, and the clearance between the tip of the rotor and the bottom surface and side wall of the can body is minimized to the extent that it does not interfere with the rotation of the rotor. The stirring blade generates particles by applying centrifugal force and upward driving force to the slurry.
[0057] As for the rotation conditions of the rotor blades, the lower limit of the peripheral speed is preferably 0.5 m / sec, or 0.7 m / sec, or 1 m / sec, or 3 m / sec, or 6 m / sec, and the upper limit is preferably 40 m / sec, or 30 m / sec, or 20 m / sec, or 15 m / sec, or 14 m / sec, or 13 m / sec, or 12 m / sec. The peripheral speed does not need to be constant during the granulation process, and may be changed within a preferred range. By setting the peripheral speed within a preferred range, a dry powder of cellulose fibers with excellent redispersibility can be obtained. A peripheral speed below the upper limit is preferred from the viewpoint of preventing deterioration of physical properties due to a decrease in crystallinity of cellulose. A peripheral speed above the lower limit is preferred from the viewpoint of improving the efficiency of pulverizing the slurry during drying with the chopper blade.
[0058] The shear rate applied to the slurry by the stirring blade is 50 sec -1 ~7000sec ‐1 , or 150 seconds -1 ~5000sec ‐1 , or 250sec -1 ~3500sec ‐1 Examples include:
[0059] The chopper blade may have one or more chopper blades extending outward from the rotating shaft, and may have a multi-stage structure with multiple chopper blades. The rotating shaft may protrude inward from the side wall of the can body in a cantilevered manner, or may penetrate the can body horizontally (i.e., a through-type chopper blade may be formed). A plurality of chopper blades may be arranged at predetermined intervals in the direction of the rotating shaft.
[0060] As for the grinding conditions using a chopper blade, the lower limit of the chopper rotation speed is preferably 10 rpm, or 50 rpm, or 100 rpm, or 200 rpm, or 500 rpm, or 1000 rpm, and the upper limit is preferably 6000 rpm, or 5000 rpm, or 4500 rpm, or 4000 rpm. By setting the chopper rotation speed within a preferred range, a dry powder of cellulose fiber with excellent redispersibility can be obtained. It is preferable that the chopper rotation speed is equal to or lower than the upper limit from the viewpoint of preventing deterioration of physical properties due to a decrease in crystallinity of cellulose. It is preferable that the chopper rotation speed is equal to or higher than the lower limit from the viewpoint of obtaining a good grinding effect of the chopper.
[0061] In one embodiment, the lower limit of the peripheral speed of the chopper blade is preferably 0.5 m / sec, or 0.7 m / sec, or 1 m / sec, or 3 m / sec, or 6 m / sec, and the upper limit is preferably 40 m / sec, 30 m / sec, 20 m / sec, 15 m / sec, or 14 m / sec, or 13 m / sec, or 12 m / sec. By setting the peripheral speed of the chopper blade within a preferred range, a dry powder of cellulose fiber having excellent redispersibility can be obtained. It is preferable that the peripheral speed of the chopper blade is equal to or lower than the upper limit from the viewpoint of preventing deterioration of physical properties due to a decrease in crystallinity of cellulose. It is preferable that the peripheral speed of the chopper blade is equal to or higher than the lower limit from the viewpoint of obtaining a good grinding effect of the chopper.
[0062] When the chopper blade and the stirring blade are on different rotating shafts, the chopper blade / stirring blade ratio of the rotation diameter and the peripheral speed may be set arbitrarily as desired, for example, 1.0 / 1.0 to 0.1 / 1.0, or 0.5 / 1.0 to 0.1 / 1.0, or 0.5 / 1.0 to 0.2 / 1.0, or 0.5 / 1.0 to 0.3 / 1.0. In one embodiment, the peripheral speed of the chopper blade is equal to or less than the peripheral speed of the stirring blade, or is smaller than the peripheral speed of the stirring blade. When the diameter and peripheral speed of the chopper blade are equal to or less than the diameter and peripheral speed of the stirring blade, the convection of the slurry by the stirring blade is not disturbed, and the control of the powder shape is easy, which is preferable. When the diameter and peripheral speed of the chopper blade are 1 / 10 or more of the diameter and peripheral speed of the stirring blade, the crushing effect by the chopper blade is high, which is preferable.
[0063] On the other hand, when the chopper blade and the stirring blade are on the same rotating shaft, it is preferable that their rotational speeds are equal. It is also preferable that the rotation diameter of the chopper blade is equal to or less than the rotation diameter of the stirring blade, and it is preferable that the circumferential speed of the chopper blade is equal to or less than the circumferential speed of the stirring blade. When the rotation diameter of the chopper blade is larger than the rotation diameter of the stirring blade, and when the circumferential speed of the chopper blade is larger than the circumferential speed of the stirring blade, the upward driving force by the stirring blade decreases, and the stirring efficiency tends to be low. When the chopper blade and the stirring blade are on the same rotating shaft, the chopper blade / stirring blade ratio of the rotation diameter and the circumferential speed is preferably 1.0 / 1.0 to 0.5 / 1.0, or 0.95 / 1.0 to 0.5 / 1.0, or 0.95 / 1.0 to 0.6 / 1.0. In one aspect, the circumferential speed of the chopper blade is equal to or less than the circumferential speed of the stirring blade, or is smaller than the circumferential speed of the stirring blade.
[0064] Even when the chopper blade and the stirring blade are on the same rotating shaft, the slurry or particles are convected in the can body by the centrifugal force and upward driving force of the lower blade corresponding to the stirring blade, and are dried under reduced pressure to generate particles. In the process, the particles are crushed by the shear force of the upper blade corresponding to the chopper blade, and the crushed particles return to the vicinity of the stirring blade and are stirred again, increasing the particle size and gradually granulating. Therefore, even if there are two or more blades on the same rotating shaft, the lower blade plays the role of the stirring blade and the upper blade plays the role of the chopper blade. When the diameter and circumferential speed of the chopper blade are less than the diameter and circumferential speed of the stirring blade, it is preferable because the stirring blade easily generates convection of the slurry and the slurry is less likely to remain in the corners of the can body. When the diameter and circumferential speed of the chopper blade are more than half of the diameter and circumferential speed of the stirring blade, the crushing effect by the chopper blade is high and it is preferable.
[0065] As conditions for the reduced pressure drying in the granulation step, the lower limit of the jacket temperature is preferably 20°C or more, or 30°C or more, or 40°C or more, or 50°C or more from the viewpoint of increasing the drying rate and improving production efficiency, and the upper limit is 160°C or less, or 150°C or less, or 140°C or less, or 130°C or less from the viewpoint of the thermal stability of the cellulose fibers and additives. The lower limit of the reduced pressure is preferably -1 kPa or more, or -10 kPa or more, -20 kPa or more, -30 kPa or more, -40 kPa or more, or -50 kPa or more, and the upper limit is preferably -100 kPa or less, -95 kPa or less, or -90 kPa or less. The pressure may be adjusted by fully operating a vacuum pump having an appropriate exhaust capacity, or air and / or an inert gas may be intentionally introduced using a vacuum regulator, a leak valve, or the like. When air and / or an inert gas is introduced, it is preferable to provide an intake section in the can body or upstream of the can body because the medium vapor can be efficiently exhausted.
[0066] Since cellulose fibers are very susceptible to agglomeration in a dry state, in a typical dry powder of cellulose fibers, the cellulose fibers are strongly agglomerated to each other, and are not easily redispersed even when the dry powder is redispersed in a dispersion medium. In the granulation step of the method disclosed herein, granulation is performed by stirring, so the shear force applied to the slurry and the generated particles is relatively small, and the cellulose fibers aggregate to generate coarse particles. The generated coarse particles are refined by chopper pulverization, and the finely refined particles are further subjected to stirring to increase their particle size. If coarse particles are generated by this stirring, they are refined again by chopper pulverization. In chopper pulverization, coarse particles are pulverized, but particles that are originally fine are not further pulverized, so that a dry powder with reduced particle size variation can be obtained by repeating particle generation by stirring and chopper pulverization. In addition, by chopping cellulose fiber particles, the cellulose fibers on the particle surface can be fluffed (i.e., a sparse structure can be formed on the particle surface), and by repeating this chopper grinding with stirring, a dry powder that has the desired particle size but is sparse (i.e., has a low bulk density) can be produced.
[0067] In terms of stirring efficiency, the slurry at the start of the granulation step preferably contains 5% by mass or more, 20% by mass or more, 40% by mass or more, or 60% by mass or more of the liquid medium. In terms of process efficiency, the amount of the liquid medium in the slurry at the start of the granulation step may be 95% by mass or less, 90% by mass or less, or 80% by mass or less.
[0068] The slurry at the start of the granulation step preferably contains water in an amount of 5% by mass or more, 20% by mass or more, 40% by mass or more, or 60% by mass or more in terms of stirring efficiency. The amount of water in the slurry at the start of the granulation step may be 95% by mass or less, 90% by mass or less, or 80% by mass or less in terms of process efficiency.
[0069] In the granulation step when the liquid medium in the slurry contains water, it is preferable to add an additional medium, which is a liquid medium other than water, to the slurry. Examples of the additional medium include various organic solvents as exemplified in the section <Slurry preparation step>. The additional medium is preferably one or more mediums selected from the group consisting of alcohols (e.g., methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, s-butanol, t-butanol, etc.) having a boiling point of 50°C to 170°C; ethers (e.g., propylene glycol monomethyl ether, 1,2-dimethoxyethane, diisopropyl ether, tetrahydrofuran, 1,4-dioxane, etc.); carboxylic acids (e.g., formic acid, acetic acid, lactic acid, etc.); esters (e.g., ethyl acetate, vinyl acetate, etc.); ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, etc.); and nitrogen-containing solvents (dimethylformamide, dimethylacetamide, acetonitrile, etc.), with t-butanol, s-butanol, i-butanol, acetone, etc. being more preferred. It is preferable that these organic solvents are substances that form an azeotrope with water. In particular, it is more preferable that the azeotropic mixture has a minimum azeotropic point lower than the boiling points of water and the organic solvent alone, because the water can be easily dried even at low vacuum and / or temperature. The timing of addition is preferably midway through the granulation process, for example, after the water in the slurry has reached 80% by mass or less, or 70% by mass or less, or 60% by mass or less, or 50% by mass or less, or 40% by mass or less, or 30% by mass or less, or 20% by mass or less, or 10% by mass or less. When water remains at these ratios, the additional medium is replaced with water to suppress aggregation of the cellulose fibers, and a dry powder having a desired particle size and good redispersibility can be formed.
[0070] In a preferred embodiment, the additional medium is added to the slurry in a range of 1:99 to 90:10 in the mass ratio of water to additional medium in the slurry. More preferably, the mass ratio is 1:99 to 80:20, or 1:99 to 70:30, or 5:95 to 70:30, or 5:95 to 60:40, or 10:90 to 60:40. By adding the additional medium in the above range, it is possible to suppress strong aggregation between cellulose fibers at a microscopic level of, for example, 10 μm or less, while promoting granulation at a level of more than 10 μm to 1000 μm or less, so that it is possible to achieve both good progress of the granulation process and good redispersibility of the obtained dry powder. When the additional medium is a substance that forms an azeotropic mixture with water, it is preferable to add the additional medium to the slurry in a ratio higher than the azeotropic composition ratio with water (i.e., the minimum ratio of the additional medium that can form an azeotropic mixture with water).
[0071] In another preferred embodiment, the additional medium is added to the slurry two or more times. By repeating the addition of the additional medium and drying in the granulation process, the replacement of moisture with the additional medium progresses, and additives such as binders are uniformly mixed with the cellulose fibers, making it possible to achieve both good redispersibility and binder function of the obtained dry powder.
[0072] In another embodiment, the granulation step preferably includes a step of adding an additional medium at a constant flow rate per unit time while continuing the vacuum drying, from the viewpoint of reducing the amount of additional medium used and reducing the drying time. In this step, it is particularly preferable to add the additional medium at a constant flow rate per unit time so that the total liquid amount in the slurry (i.e., the total amount of water and additional medium) is maintained constant. Depending on the type of additional medium, the total liquid amount in the slurry may be increased or decreased. After such a step, further vacuum drying can be performed to reduce the total liquid amount to obtain the desired dry powder.
[0073] In the granulation process, when forming a slurry with a certain water:additional medium ratio, it is preferable from the viewpoint of the process to add the additional medium while evaporating the water, rather than adding the entire amount of the additional medium at once, since the total amount of the additional medium can be reduced. In addition, since the additional medium can be added while granulation is being performed, the replacement of the water with the additional medium is easily promoted, and a powder with good redispersibility is easily obtained. The additional liquid may be added, for example, in droplets, a mist, or the like.
[0074] The moisture content of the slurry in the granulation step can be measured by a heat drying type moisture content meter or a Karl Fischer moisture content meter. The mass ratio of water to the additional medium in the slurry after the additional medium is added is, for example, i) A method in which the moisture content in the slurry is measured using a Karl Fischer moisture meter, and the liquid content of the volatile components (water and additional medium) in the slurry is measured using a heat drying type moisture meter, and then calculated. ii) A method in which the additional medium in the slurry is extracted with a different solvent capable of dissolving the additional medium, the content of the additional medium is measured by gas chromatography, and the total liquid ratio of the volatile components (water and additional medium) in the slurry is measured and calculated using a heat drying type moisture content meter. iii) A method in which the water and additional medium in the slurry are extracted with a heavy solvent and then calculated by solution NMR.
[0075] In addition, in an embodiment in which the liquid medium in the slurry prepared in the slurry preparation step does not contain water, an additional medium may be added in the granulation step. As the additional medium, one or more selected from the group consisting of commonly used water-miscible organic solvents, such as: alcohols having a boiling point of 50°C to 170°C (e.g., methanol, ethanol, n-propanol, i-propanol, n-butanol, i-butanol, s-butanol, t-butanol, etc.); ethers (e.g., propylene glycol monomethyl ether, 1,2-dimethoxyethane, diisopropyl ether, tetrahydrofuran, 1,4-dioxane, etc.); carboxylic acids (e.g., formic acid, acetic acid, lactic acid, etc.); esters (e.g., ethyl acetate, vinyl acetate, etc.); ketones (e.g., acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclopentanone, cyclohexanone, etc.); nitrogen-containing solvents (dimethylformamide, dimethylacetamide, acetonitrile, etc.) and hydrophobic organic solvents, such as aromatic hydrocarbons (benzene, toluene, xylene, etc.); aliphatic hydrocarbons (hexane, heptane, octane, decane, etc.); halogenated hydrocarbons (tetrachloromethane, chloroform, dichloromethane, chloroethane, etc.), etc. may be used. As a preferred mode of adding the additional medium, it may be added all at once or in several portions before or after the start of granulation. For example, the additional medium may be added in the form of droplets or mist while drying under reduced pressure during granulation.
[0076] In one embodiment, the average particle size of the dry powder of cellulose fibers is preferably 1 μm or more, or 10 μm or more, or 50 μm or more, or 100 μm or more, or 200 μm or more, or 500 μm or more, and is preferably 5000 μm or less, or 4000 μm or less, or 3000 μm or less, or 2000 μm or less. The above average particle size is a value measured by a laser diffraction / scattering method or a dry sieve method.
[0077] In one aspect, the bulk density of the dry powder of cellulose fibers is 0.05 g / mL or more, or 0.06 g / mL or more, or 0.07 g / mL or more, or 0.08 g / mL or more, or 0.09 g / mL or more, or 0.10 g / mL or more from the viewpoint of ease of production and transportation efficiency of the dry powder, and is 1.0 g / mL or less, or 0.9 g / mL or less, or 0.8 g / mL or less, or 0.7 g / mL or less, or 0.6 g / mL or less from the viewpoint of good redispersibility of the dry powder. The bulk density in this disclosure is a value measured by a loose bulk density measurement method.
[0078] <Chemical modification> In one embodiment, chemically modified cellulose fibers are used as the cellulose fibers. The cellulose fibers may be chemically modified in advance, for example, at the stage of raw pulp or linter, during or after the defibration treatment, or may be chemically modified during the slurry preparation step, during or after the granulation step. In a preferred embodiment, the chemical modification is chemical modification with a hydrophobic substituent.
[0079] The cellulose modification agent can be a compound that reacts with the hydroxyl group of cellulose, and includes an esterification agent, an etherification agent, and a silylating agent. In a preferred embodiment, the chemical modification is acylation using an esterification agent. The esterification agent is preferably an acid halide, an acid anhydride, a vinyl carboxylate, or a carboxylic acid.
[0080] The acid halide may be at least one selected from the group consisting of compounds represented by the following formula (1). R 1 -C(=O)-X (1) (In the formula, R 1 represents an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, a cycloalkyl group having 3 to 24 carbon atoms, or an aryl group having 6 to 24 carbon atoms, and X is Cl, Br, or I. Specific examples of acid halides include, but are not limited to, acetyl chloride, acetyl bromide, acetyl iodide, propionyl chloride, propionyl bromide, propionyl iodide, butyryl chloride, butyryl bromide, butyryl iodide, benzoyl chloride, benzoyl bromide, and benzoyl iodide. Among them, acid chlorides can be preferably used in terms of reactivity and handling. In addition, in the reaction of acid halides, one or more alkaline compounds may be added to act as a catalyst and neutralize the by-product acidic substances. Specific examples of alkaline compounds include, but are not limited to, tertiary amine compounds such as triethylamine and trimethylamine; and nitrogen-containing aromatic compounds such as pyridine and dimethylaminopyridine.
[0081] As the acid anhydride, any suitable acid anhydride can be used, for example, saturated aliphatic monocarboxylic anhydrides such as acetic acid, propionic acid, (iso)butyric acid, valeric acid, etc., unsaturated aliphatic monocarboxylic anhydrides such as (meth)acrylic acid, oleic acid, etc., alicyclic monocarboxylic anhydrides such as cyclohexanecarboxylic acid, tetrahydrobenzoic acid, etc., aromatic monocarboxylic anhydrides such as benzoic acid, 4-methylbenzoic acid, etc., Examples of dibasic carboxylic acid anhydrides include saturated aliphatic dicarboxylic acid anhydrides such as succinic anhydride and adipic acid, unsaturated aliphatic dicarboxylic acid anhydrides such as maleic anhydride and itaconic anhydride, alicyclic dicarboxylic acid anhydrides such as 1-cyclohexene-1,2-dicarboxylic acid anhydride, hexahydrophthalic anhydride and methyltetrahydrophthalic anhydride, and aromatic dicarboxylic acid anhydrides such as phthalic anhydride and naphthalic anhydride; Examples of polybasic carboxylic acid anhydrides having three or more bases include polycarboxylic acids (anhydrides) such as trimellitic anhydride and pyromellitic anhydride. In addition, in the reaction of an acid anhydride, one or more types of acidic compounds such as sulfuric acid, hydrochloric acid, phosphoric acid, etc., or Lewis acids (for example, Lewis acid compounds represented by MYn, where M represents a semimetal element such as B, As, Ge, etc., or a base metal element such as Al, Bi, In, etc., or a transition metal element such as Ti, Zn, Cu, etc., or a lanthanoid element, n is an integer corresponding to the atomic valence of M and represents 2 or 3, and Y represents a halogen atom, OAc, OCOCF3, ClO4, SbF6, PF6, or OSO2CF3(OTf)), or alkaline compounds such as triethylamine, pyridine, etc. may be added as a catalyst.
[0082] The vinyl carboxylate may be represented by the following formula (1): R-COO-CH=CH2…Formula (1) Preferred is a vinyl carboxylate represented by the formula: {wherein R is any one of an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, a cycloalkyl group having 3 to 16 carbon atoms, and an aryl group having 6 to 24 carbon atoms.} The vinyl carboxylate is more preferably at least one selected from the group consisting of vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl cyclohexanecarboxylate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, vinyl octylate, divinyl adipate, vinyl methacrylate, vinyl crotonate, vinyl pivalate, vinyl octylate, vinyl benzoate, and vinyl cinnamate. In the esterification reaction with a vinyl carboxylate, one or more catalysts selected from the group consisting of alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkaline earth metal carbonates, alkali metal hydrogencarbonates, primary to tertiary amines, quaternary ammonium salts, imidazole and derivatives thereof, pyridine and derivatives thereof, and alkoxides may be added.
[0083] Examples of the alkali metal hydroxides and alkaline earth metal hydroxides include sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, barium hydroxide, etc. Examples of the alkali metal carbonates, alkaline earth metal carbonates, and alkali metal hydrogen carbonates include lithium carbonate, sodium carbonate, potassium carbonate, cesium carbonate, magnesium carbonate, calcium carbonate, barium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, cesium hydrogen carbonate, etc.
[0084] The primary, secondary and tertiary amines refer to primary, secondary and tertiary amines, and specific examples thereof include ethylenediamine, diethylamine, proline, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethyl-1,3-propanediamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, tris(3-dimethylaminopropyl)amine, N,N-dimethylcyclohexylamine and triethylamine.
[0085] Examples of imidazole and its derivatives include 1-methylimidazole, 3-aminopropylimidazole, and carbonyldiimidazole.
[0086] Examples of pyridine and its derivatives include N,N-dimethyl-4-aminopyridine and picoline.
[0087] Examples of the alkoxide include sodium methoxide, sodium ethoxide, and potassium t-butoxide.
[0088] The carboxylic acid may be at least one selected from the group consisting of compounds represented by the following formula (1). R-COOH …(1) (In the formula, R represents an alkyl group having 1 to 16 carbon atoms, an alkenyl group having 2 to 16 carbon atoms, a cycloalkyl group having 3 to 16 carbon atoms, or an aryl group having 6 to 16 carbon atoms.)
[0089] Specific examples of carboxylic acids include at least one selected from the group consisting of acetic acid, propionic acid, butyric acid, caproic acid, cyclohexane carboxylic acid, caprylic acid, capric acid, lauric acid, myristic acid, palmitic acid, stearic acid, pivalic acid, methacrylic acid, crotonic acid, pivalic acid, octylic acid, benzoic acid, and cinnamic acid.
[0090] Among these carboxylic acids, at least one selected from the group consisting of acetic acid, propionic acid, and butyric acid, and particularly acetic acid, is preferred from the viewpoint of reaction efficiency. In addition, in the reaction of carboxylic acid, one or more types of acidic compounds such as sulfuric acid, hydrochloric acid, phosphoric acid, etc., or Lewis acids (for example, Lewis acid compounds represented by MYn, where M represents a semimetal element such as B, As, Ge, etc., or a base metal element such as Al, Bi, In, etc., or a transition metal element such as Ti, Zn, Cu, etc., or a lanthanoid element, n is an integer corresponding to the atomic valence of M and represents 2 or 3, and Y represents a halogen atom, OAc, OCOCF3, ClO4, SbF6, PF6, or OSO2CF3(OTf)), or alkaline compounds such as triethylamine, pyridine, etc. may be added as a catalyst.
[0091] Among these esterification reactants, at least one selected from the group consisting of acetic anhydride, propionic anhydride, butyric anhydride, vinyl acetate, vinyl propionate, vinyl butyrate, and acetic acid, and among these, acetic anhydride and vinyl acetate are preferred from the viewpoint of reaction efficiency.
[0092] When cellulose fibers are hydrophobized (for example, by chemical modification such as acylation), the redispersibility of the dry powder tends to be good, but the dry powder of cellulose fibers obtained by the method of the present disclosure is advantageous in that it can exhibit good redispersibility even if it is unsubstituted or has a low degree of substitution. Thus, in one embodiment, the average degree of substitution (DS) of the dry powder of cellulose fibers (average number of substituted hydroxyl groups per glucose, which is the basic building block of cellulose) can be 0.5 or less, or 0.3 or less, or 0. On the other hand, the average degree of substitution (DS) may be 0.2 or more, or 0.4 or more, or 0.6 or more, depending on the intended use of the cellulose fibers.
[0093] When the modifying group of the chemically modified cellulose fiber is an acyl group, the degree of acyl substitution (DS) can be calculated from the reflection infrared absorption spectrum of the esterified cellulose fiber based on the peak intensity ratio between the peak derived from the acyl group and the peak derived from the cellulose skeleton. The peak of the absorption band of C=O based on the acyl group is at 1730 cm -1 The absorption band of CO based on the cellulose backbone appears at 1030 cm -1 The DS of esterified cellulose fibers is calculated by plotting a correlation graph between the DS obtained from solid-state NMR measurements of esterified cellulose fibers (described later) and the modification ratio (IR index 1030), which is defined as the ratio of the peak intensity of the absorption band of C=O based on acyl groups to the peak intensity of the absorption band of CO in the cellulose backbone chain, and then calculating the calibration curve from the correlation graph. Degree of substitution DS = 4.13 × IR index (1030) It can be found by using
[0094] The method for calculating the DS of esterified cellulose fiber by solid-state NMR is as follows: 13 C solid-state NMR measurement was performed, and the intensity can be calculated using the area intensity (Inf) of a signal assigned to one carbon atom derived from the modifying group relative to the total area intensity (Inp) of signals assigned to carbons C1-C6 derived from the pyranose ring of cellulose, which appear in the range from 50 ppm to 110 ppm, using the following formula. DS = (Inf) x 6 / (Inp) For example, when the modifying group is an acetyl group, the signal at 23 ppm assigned to -CH3 may be used. Use 13 The conditions for the C solid-state NMR measurement are, for example, as follows: Equipment:Bruker Biospin Avance500WB Frequency: 125.77MHz Measurement method: DD / MAS method Waiting time: 75sec NMR sample tube: 4mmφ Accumulation times: 640 times (approx. 14 hours) MAS: 14,500Hz Chemical shift reference: glycine (external reference: 176.03 ppm)
[0095] The DS heterogeneity ratio (DSs / DSt), defined as the ratio of the degree of modification (DSs) of the fiber surface to the degree of modification (DSt) of the entire fiber of the chemically modified cellulose fiber (which is synonymous with the above-mentioned degree of acyl substitution (DS)), is preferably 1.05 or more. The larger the value of the DS heterogeneity ratio, the more pronounced the heterogeneous structure resembling a sheath-core structure (i.e., a structure in which the fiber surface layer is highly chemically modified while the fiber center retains a structure close to the original unmodified cellulose structure), and while maintaining high tensile strength and dimensional stability derived from cellulose, it is possible to improve the affinity with the resin when composited with the resin and to improve the dimensional stability of the resin composition. The DS heterogeneity ratio is more preferably 1.1 or more, or 1.2 or more, or 1.3 or more, or 1.5 or more, or 2.0 or more, and from the viewpoint of ease of production of the chemically modified cellulose fiber, it is preferably 30 or less, or 20 or less, or 10 or less, or 6 or less, or 4 or less, or 3 or less. The value of DSs varies depending on the degree of modification of the esterified cellulose, but as an example, it is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, even more preferably 0.5 or more, and is preferably 3.0 or less, more preferably 2.5 or less, particularly preferably 2.0 or less, even more preferably 1.5 or less, particularly preferably 1.2 or less, and most preferably 1.0 or less. The preferred range of DSt is as described above for the acyl substituent (DS).
[0096] The smaller the coefficient of variation (CV) of the DS heterogeneity of the chemically modified cellulose fiber, the smaller the variation in various physical properties of the resin composition, and therefore the more preferable. The coefficient of variation is preferably 50% or less, or 40% or less, or 30% or less, or 20% or less. The coefficient of variation can be further reduced, for example, by a method in which the cellulose raw material is defibrated and then chemically modified to obtain the chemically modified cellulose fiber (i.e., a sequential method), whereas it can be increased by a method in which the defibration and chemical modification of the cellulose raw material are simultaneously performed (i.e., a simultaneous method). Although the mechanism of this action is not clear, it is considered that in the simultaneous method, chemical modification is more likely to proceed in the thin fibers generated in the early stage of defibration, and when hydrogen bonds between cellulose microfibrils are reduced by chemical modification, defibration proceeds further, resulting in an increase in the coefficient of variation of the DS heterogeneity.
[0097] The coefficient of variation (CV) of the DS heterogeneity ratio is calculated by taking 100 g of an aqueous dispersion of chemically modified cellulose fiber (solid content of 10 mass% or more), freeze-pulverizing 10 g each to prepare measurement samples, calculating the DS heterogeneity ratio from the DSt and DSs of the 10 samples, and then using the standard deviation (σ) and arithmetic mean (μ) of the DS heterogeneity ratio among the obtained 10 samples, using the following formula: DS heterogeneity ratio = DSs / DSt Coefficient of variation (%) = standard deviation σ / arithmetic mean μ × 100
[0098] The DSs is calculated as follows. That is, the esterified cellulose powdered by freeze-pulverization is placed on a dish-shaped sample stage with a diameter of 2.5 mm, the surface is pressed down to make it flat, and then measurement is performed by X-ray photoelectron spectroscopy (XPS). The XPS spectrum reflects the constituent elements and chemical bond state of only the surface layer of the sample (typically about a few nm). Peak separation is performed on the obtained C1s spectrum, and DSs can be calculated by the following formula based on the area intensity (Ixf) of the peak assigned to one carbon atom derived from the modifying group relative to the area intensity (Ixp) of the peak (289 eV, CC bond) assigned to carbons C2-C6 derived from the pyranose ring of cellulose. DSs = (Ixf) x 5 / (Ixp) For example, if the modifying group is an acetyl group, after peak separation of the C1s spectrum at 285 eV, 286 eV, 288 eV, and 289 eV, the peak at 289 eV can be used for Ixp and the peak derived from the O-C=O bond of the acetyl group (286 eV) can be used for Ixf. The conditions for the XPS measurement are as follows, for example: Equipment used: ULVAC-Phi VersaProbe II Excitation source: mono.AlKα 15kV×3.33mA Analysis size: Approx. 200 μm φ Photoelectron extraction angle: 45° Capture Area Narrow scan: C 1s, O 1s Pass Energy: 23.5eV
[0099] <Addition of binder> In one embodiment, a binder can be added to the slurry in the slurry preparation step and / or granulation step. The binder contributes to improving the affinity between the cellulose fiber and the resin in the composite. Examples of the binder include polymers having hydrophilic groups (e.g., hydroxyl groups, amino groups, etc.) (e.g., polyacrylamide, polyalkylene oxide, polyacrylic acid and its salts, polysaccharides (e.g., cellulose derivatives, starch, alginic acid and its salts (e.g., sodium alginate), guar gum, gellan gum, gelatin, etc.), polyvinyl alcohol, etc.), and monomers having hydrophilic groups (e.g., propylene glycol, N-vinylacetamide, etc.).
[0100] Examples of the alkylene oxide unit of the polyalkylene oxide include alkylene oxides having 2 to 4 carbon atoms, preferably ethylene oxide and propylene oxide. In a preferred embodiment, the polyalkylene oxide is composed of ethylene oxide units and / or propylene oxide units. A particularly preferred polyalkylene oxide is polyethylene oxide.
[0101] Examples of cellulose derivatives include cellulose ethers (for example, methyl cellulose, carboxymethyl cellulose, carboxyethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropylmethyl cellulose, etc.).
[0102] The weight average molecular weight of the binder is preferably 1,000 or more, more preferably 5,000 or more, and even more preferably 10,000 or more, and is preferably 5×10 8 Less than or equal to 1×10 8 Less than 5×10, more preferably 7 The following is the result.
[0103] In one embodiment, the binder is a surfactant. The surfactant has a chemical structure in which a portion having a hydrophilic substituent and a portion having a hydrophobic substituent are covalently bonded. As the surfactant, any of anionic surfactants, nonionic surfactants, amphoteric surfactants, and cationic surfactants can be used, but nonionic surfactants are preferred in terms of obtaining good dispersibility of cellulose fibers.
[0104] As the hydrophilic group of the surfactant, from the viewpoint of affinity with cellulose fibers, polyoxyethylene chain, carboxyl group, and hydroxyl group are preferred, and polyoxyethylene chain is particularly preferred. Nonionic polyoxyethylene derivatives are particularly preferred. The polyoxyethylene chain length of the polyoxyethylene derivative may be 1 or more, or 4 or more, or 10 or more, or 15 or more. The longer the chain length, the higher the affinity for hydrophobic cellulose fibers, but from the viewpoint of balance with the properties of the resin composite (e.g., mechanical properties, etc.), the polyoxyethylene chain length may be 60 or less, or 50 or less, or 40 or less, or 30 or less, or 20 or less.
[0105] As the structure of the hydrophobic group of the surfactant, alkyl ether type, alkyl phenyl ether type, rosin ester type, bisphenol A type, β-naphthyl type, styrenated phenyl type, and hardened castor oil type are preferred in terms of high affinity with resin. The number of carbon atoms of the alkyl chain of the hydrophobic group (in the case of alkyl phenyl, the number of carbon atoms excluding the phenyl group) is preferably 5 or more, or 10 or more, or 12 or more, or 16 or more. For example, when the resin is a polyolefin resin, the more carbon atoms of the surfactant, the higher the affinity with the resin. The number of carbon atoms may be, for example, 30 or less, or 25 or less.
[0106] In a preferred embodiment, the binder is one or more compounds selected from the group consisting of polyalkylene oxides and cellulose derivatives, and particularly preferably one or more compounds selected from the group consisting of polyalkylene oxides, cellulose ethers, and cellulose esters.
[0107] The binder is preferably dissolved in a medium and added to the slurry in order to facilitate uniform mixing in the slurry preparation step and / or granulation step. The medium used can be selected from water and those exemplified as additional media in this disclosure. When the binder is added in the slurry preparation step, it is preferably of the same composition as the medium used in the slurry preparation step, and when the binder is added in the granulation step, it is preferably of the same composition as the medium used in the granulation step.
[0108] The amount of binder may be, relative to 100 parts by mass of cellulose fibers, preferably 5 parts by mass or more, or 10 parts by mass or more, or 20 parts by mass or more, or 30 parts by mass or more, or 40 parts by mass or more, and may be preferably 100 parts by mass or less, or 70 parts by mass or less, or 50 parts by mass or less.
[0109] The dry powder produced by the method of the present disclosure, which has good redispersibility in a dispersion medium, can be dispersed well in a resin, for example, when the cellulose fiber and the resin are composited, and therefore has an excellent effect of improving the physical properties of a resin composite containing the cellulose fiber and the resin. In one embodiment, the dry powder of the cellulose fiber of the present disclosure is subjected to chopper pulverization, and thus fiber fluff is likely to remain on the powder surface. Such a sparse structure on the powder surface can promote the penetration of the dispersion medium into the powder during redispersion, contributing to improved redispersibility.
[0110] In one embodiment, when a redispersion liquid is prepared by dispersing the dry powder in a liquid medium of the same type and amount as the slurry produced in the slurry preparation step, the shear rate 100s of the redispersion liquid is -1 The viscosity at is the shear rate of the slurry obtained in the slurry preparation process. -1 The viscosity is 30% or more of the above-mentioned viscosity at 100° C. The above ratio is an index showing the extent to which the dispersibility of the cellulose fibers before drying can be reproduced after redispersion (i.e., redispersibility). The above ratio is preferably 40% or more, 50% or more, or 60% or more. The higher the ratio, the better, and it is most preferably 100%, but from the viewpoint of ease of production of the cellulose fibers, it may be, for example, 90% or less, or 80% or less.
[0111] Redispersion shear rate 100s -1 The viscosity at may be preferably 6 mPa s or more, or 7.5 mPa s or more, or 9 mPa s or more, in order that the cellulose fibers are highly dispersed, and may be preferably 13.5 mPa s or less, or 12 mPa s or less, in order that the redispersion liquid can be suitably used, for example, in the production of a resin composite.
[0112] <Method for producing resin composite> One aspect of the present invention provides a method for producing a resin composite comprising cellulose fibers and a resin, the method comprising preparing a dry powder of cellulose fibers as described above, and mixing the dry powder with a resin.
[0113] <Resin> The resin may be a thermoplastic resin, a thermosetting resin, or a photocurable resin. The resin may be an elastomer. From the viewpoints of moldability and productivity, a thermoplastic resin is more preferable.
[0114] (thermoplastic resin) When the resin is a thermoplastic resin, the melting point of the thermoplastic resin may be appropriately selected depending on the application of the resin composite, etc. The melting point of the thermoplastic resin can be, for example, 150°C to 190°C or 160°C to 180°C for a resin with a relatively low melting point (e.g., polyolefin resin), and 220°C to 350°C or 230°C to 320°C for a resin with a relatively high melting point (e.g., polyamide resin).
[0115] The thermoplastic resin may preferably be at least one selected from the group consisting of polyolefin-based resins, polyacetate-based resins, polycarbonate-based resins, polyamide-based resins, polyester-based resins, polyphenylene ether-based resins, and acrylic-based resins.
[0116] The polyolefin resin preferred as the thermoplastic resin is a polymer obtained by polymerizing olefins (e.g., α-olefins) and / or alkenes as monomer units.Specific examples of the polyolefin resin include ethylene (co)polymers such as low-density polyethylene (e.g., linear low-density polyethylene), high-density polyethylene, ultra-low-density polyethylene, and ultra-high-molecular-weight polyethylene, polypropylene (co)polymers such as polypropylene, ethylene-propylene copolymer, and ethylene-propylene-diene copolymer, and copolymers of ethylene and α-olefins such as ethylene-acrylic acid copolymer, ethylene-methyl methacrylate copolymer, and ethylene-glycidyl methacrylate copolymer.
[0117] Here, the most preferred polyolefin resin is polypropylene. In particular, polypropylene having a melt mass flow rate (MFR) of 3 g / 10 min or more and 30 g / 10 min or less, measured at 230° C. and a load of 21.2 N according to ISO1133, is preferred. The lower limit of MFR is more preferably 5 g / 10 min, even more preferably 6 g / 10 min, and most preferably 8 g / 10 min. The upper limit is more preferably 25 g / 10 min, even more preferably 20 g / 10 min, and most preferably 18 g / 10 min. From the viewpoint of improving the toughness of the resin composite, it is desirable that the MFR does not exceed the above upper limit, and from the viewpoint of the fluidity of the resin composite, it is desirable that the MFR does not exceed the above lower limit.
[0118] In addition, in order to increase the affinity with cellulose fibers, an acid-modified polyolefin resin can also be suitably used. As the acid used for the acid modification, a mono- or polycarboxylic acid can be used, and examples thereof include maleic acid, fumaric acid, succinic acid, phthalic acid and their anhydrides, and citric acid. Maleic acid or its anhydride is particularly preferred because it is easy to increase the modification rate. There is no particular restriction on the modification method, but a method in which a polyolefin resin is heated to a melting point or higher in the presence or absence of a peroxide and melt-kneaded is generally used. As the polyolefin resin to be acid-modified, all of the above-mentioned polyolefin resins can be used, but polypropylene is particularly suitable. The acid-modified polypropylene resin may be used alone, but it is more preferable to use it in combination with an unmodified polypropylene resin in order to adjust the modification rate of the resin as a whole. In this case, the ratio of the acid-modified polypropylene resin to all polypropylene resins is preferably 0.5% by mass to 50% by mass. A more preferred lower limit is 1 mass%, or 2 mass%, or 3 mass%, or 4 mass%, or 5 mass%. A more preferred upper limit is 45 mass%, or 40 mass%, or 35 mass%, or 30 mass%, or 20 mass%. In order to maintain the interfacial strength between the resin and the cellulose fibers, a content equal to or greater than the lower limit is preferred, and in order to maintain the ductility of the resin, a content equal to or less than the upper limit is preferred.
[0119] The melt mass flow rate (MFR) of the acid-modified polypropylene resin measured in accordance with ISO 1133 at 230° C. and a load of 21.2 N is preferably 50 g / 10 min or more, 100 g / 10 min or more, 150 g / 10 min or more, or 200 g / 10 min or more from the viewpoint of enhancing the affinity at the interface between the resin and the cellulose fiber. The upper limit is not particularly limited, but is preferably 500 g / 10 min from the viewpoint of maintaining mechanical strength.
[0120] Examples of polyamide-based resins that are preferable as the thermoplastic resin include polyamides obtained by polycondensation reaction of lactams (e.g., polyamide 6, polyamide 11, polyamide 12, etc.); diamines (e.g., 1,6-hexanediamine, 2-methyl-1,5-pentanediamine, 1,7-heptanediamine, 2-methyl-1-6-hexanediamine, 1,8-octanediamine, 2-methyl-1,7-heptanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, m-xylylenediamine, etc.) and dicarboxylic acids (e.g., butanedioic acid, pentanedioic acid, hexanedioic acid, , heptanedioic acid, octanedioic acid, nonanedioic acid, decanedioic acid, benzene-1,2-dicarboxylic acid, benzene-1,3-dicarboxylic acid, benzene-1,4-dicarboxylic acid, cyclohexane-1,3-dicarboxylic acid, cyclohexane-1,4-dicarboxylic acid, etc.) (for example, polyamide 6,6, polyamide 6,10, polyamide 6,11, polyamide 6,12, polyamide 6,T, polyamide 6,I, polyamide 9,T, polyamide 10,T, polyamide 2M5,T, polyamide MXD,6, polyamide 6,C, polyamide 2M5,C, etc.); and copolymers in which these are copolymerized (for example, polyamide 6,T / 6,I, etc.).
[0121] Among these polyamide resins, aliphatic polyamides such as polyamide 6, polyamide 11, polyamide 12, polyamide 6,6, polyamide 6,10, polyamide 6,11, and polyamide 6,12, and alicyclic polyamides such as polyamide 6,C and polyamide 2M5,C are more preferred.
[0122] From the viewpoint of improving the heat resistance of the resin composite, the melting point of the polyamide resin is preferably 220°C or more, or 230°C or more, or 240°C or more, or 245°C or more, or 250°C or more, and from the viewpoint of ease of production of the resin composite, the melting point is preferably 350°C or less, or 320°C or less, or 300°C or less.
[0123] The terminal carboxyl group concentration of the polyamide resin is not particularly limited, but is preferably 20 μmol / g or more, or 30 μmol / g or more, and preferably 150 μmol / g or less, or 100 μmol / g or less, or 80 μmol / g or less.
[0124] In the polyamide resin, the ratio of carboxyl end groups to all end groups ([COOH] / [total end groups]) is preferably 0.30 or more, or 0.35 or more, or 0.40 or more, or 0.45 or more from the viewpoint of dispersibility of cellulose fibers in the resin composite, and is preferably 0.95 or less, or 0.90 or less, or 0.85 or less, or 0.80 or less from the viewpoint of color tone of the resin composite.
[0125] The terminal group concentration of the polyamide resin can be adjusted by a known method, such as adding a terminal regulator (e.g., a diamine compound, a monoamine compound, a dicarboxylic acid compound, a monocarboxylic acid compound, an acid anhydride, a monoisocyanate, a monoacid halide, a monoester, a monoalcohol, etc.) that reacts with the terminal group during polymerization of the polyamide to the polymerization liquid so as to obtain a predetermined terminal group concentration.
[0126] Examples of the terminal regulator that reacts with the terminal amino group include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid; and mixtures of a plurality of terminal regulators selected from the above. Among these, from the viewpoints of reactivity, stability of the blocked terminal, and cost, one or more terminal regulators selected from the group consisting of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, and benzoic acid are preferred, and acetic acid is most preferred.
[0127] Examples of the terminal regulator that reacts with the terminal carboxyl group include aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, etc., alicyclic monoamines such as cyclohexylamine, dicyclohexylamine, etc., aromatic monoamines such as aniline, toluidine, diphenylamine, naphthylamine, etc., and any mixtures thereof. Among these, one or more terminal regulators selected from the group consisting of butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, and aniline are preferred in terms of reactivity, boiling point, stability of the blocked terminal, price, etc.
[0128] The concentration of amino end groups and carboxyl end groups of the polyamide resin is 1 It can be determined from the integral value of the characteristic signal corresponding to each terminal group by H-NMR. This method is preferable in terms of accuracy and simplicity. More specifically, it is recommended to use the method described in JP-A-7-228775, use deuterated trifluoroacetic acid as the measurement solvent, and set the number of integration scans to 300 or more.
[0129] The intrinsic viscosity [η] of the polyamide resin measured under the condition of 30°C in concentrated sulfuric acid is preferably 0.6 to 2.0 dL / g, or 0.7 to 1.4 dL / g, or 0.7 to 1.2 dL / g, or 0.7 to 1.0 dL / g, from the viewpoint that the fluidity in the mold is good and the appearance of the molded piece is good when the resin composite is, for example, injection molded. In the present disclosure, the "intrinsic viscosity" is synonymous with the viscosity generally called the limiting viscosity. The intrinsic viscosity is obtained by measuring the ηsp / c of several measurement solvents having different concentrations under the temperature condition of 30°C in 96% concentrated sulfuric acid, deriving the relational equation between each of the ηsp / c and the concentration (c), and extrapolating the concentration to zero. The value extrapolated to zero is the intrinsic viscosity. Details of the above method are described, for example, in Polymer Process Engineering (Prentice-Hall, Inc. 1994), pages 291 to 294, etc. From the viewpoint of accuracy, it is desirable to set the concentrations in the measurement solvents having different concentrations to at least four points (for example, 0.05 g / dL, 0.1 g / dL, 0.2 g / dL, and 0.4 g / dL).
[0130] As the polyester resin preferred as the thermoplastic resin, one or more selected from polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), polyhydroxyalkanoic acid (PHA), polylactic acid (PLA), polyarylate (PAR), etc. can be used. Among them, PET, PBS, PBSA, PBT and PEN are more preferred, and PBS, PBSA and PBT are particularly preferred.
[0131] The terminal groups of the polyester resin can be arbitrarily changed by the monomer ratio during polymerization, the presence or absence and amount of addition of a terminal stabilizer, etc. The ratio of carboxyl terminal groups to all terminal groups of the polyester resin ([COOH] / [total terminal groups]) is preferably 0.30 or more, or 0.35 or more, or 0.40 or more, or 0.45 or more from the viewpoint of dispersibility of cellulose fibers in the resin composite, and is preferably 0.95 or less, or 0.90 or less, or 0.85 or less, or 0.80 or less from the viewpoint of color tone of the resin composite.
[0132] As the polyacetal resin preferred as the thermoplastic resin, homopolyacetal made from formaldehyde and copolyacetal containing trioxane as the main monomer and 1,3-dioxolane as the comonomer component are generally used, and although both can be used, copolyacetal is preferred from the viewpoint of thermal stability during processing. The amount of the structure derived from the comonomer component (e.g., 1,3-dioxolane) is preferably 0.01 mol% or more, or 0.05 mol% or more, or 0.1 mol% or more, or 0.2 mol% or more from the viewpoint of thermal stability during extrusion processing and molding processing, and is preferably 4 mol% or less, or 3.5 mol% or less, or 3.0 mol% or less, or 2.5 mol% or less, or 2.3 mol% or less from the viewpoint of mechanical strength.
[0133] (thermosetting resin) Examples of thermosetting resins include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol E type epoxy resin, bisphenol M type epoxy resin, bisphenol P type epoxy resin, and bisphenol Z type epoxy resin; novolac type epoxy resins such as bisphenol A novolac type epoxy resin, phenol novolac type epoxy resin, and cresol novolac epoxy resin; biphenyl type epoxy resin, biphenyl aralkyl type epoxy resin, aryl alkylene type epoxy resin, tetraphenylol ethane type epoxy resin, naphthalene type epoxy resin, anthracene type epoxy resin, phenoxy type epoxy resin, dicyclopentadiene type epoxy resin, norbornene type epoxy resin, adamantane type epoxy resin, fluorene type epoxy resin, glycidyl methacrylate copolymer epoxy resin, cyclohexylmaleimide and glycidyl methacrylate copolymer epoxy resin, epoxy modified polybutadiene rubber derivative, CTBN modified epoxy resin, trimethylolpropane polyglycidyl ether, Phenyl-1,3-diglycidyl ether, biphenyl-4,4'-diglycidyl ether, 1,6-hexanediol diglycidyl ether, diglycidyl ether of ethylene glycol or propylene glycol, sorbitol polyglycidyl ether, tris(2,3-epoxypropyl)isocyanurate, triglycidyl tris(2-hydroxyethyl)isocyanurate, novolac-type phenolic resins such as phenol novolac resin, cresol novolac resin, and bisphenol A novolac resin, unmodified resol phenolic resin, paulownia wood Examples of the resin include phenolic resins such as resol-type phenolic resins, such as oil-modified resol phenolic resins modified with oil, linseed oil, walnut oil, etc.; triazine ring-containing resins, such as phenoxy resins, urea (urea) resins, and melamine resins; unsaturated polyester resins, bismaleimide resins, diallyl phthalate resins, silicone resins, resins having a benzoxazine ring, norbornene resins, cyanate resins, isocyanate resins, urethane resins, benzocyclobutene resins, maleimide resins, bismaleimide triazine resins, polyazomethine resins, and thermosetting polyimides.
[0134] (light curing resin) Examples of photocurable resins include (meth)acrylate resins, vinyl resins, and epoxy resins. These are generally classified into radical reaction types in which a monomer reacts with radicals generated by light, and cationic reaction types in which a monomer undergoes cationic polymerization, according to the reaction mechanism. Examples of radical reaction type monomers include (meth)acrylate compounds and vinyl compounds (e.g., certain vinyl ethers). Examples of cationic reaction types include epoxy compounds and certain vinyl ethers. For example, an epoxy compound that can be used as a cationic reaction type can be a monomer for both thermosetting resins and photocurable resins.
[0135] The (meth)acrylate compound is a compound having one or more (meth)acrylate groups in the molecule. Examples of the (meth)acrylate compound include monofunctional (meth)acrylates, polyfunctional (meth)acrylates, epoxy acrylates, polyester acrylates, and urethane acrylates.
[0136] Examples of vinyl compounds include vinyl ether, styrene, and styrene derivatives. Examples of vinyl ether include ethyl vinyl ether, propyl vinyl ether, hydroxyethyl vinyl ether, and ethylene glycol divinyl ether. Examples of styrene derivatives include methyl styrene and ethyl styrene. Other examples of vinyl compounds include triallyl isocyanurate and trimethallyl isocyanurate.
[0137] As a raw material for the photocurable resin, a so-called reactive oligomer may be used. Examples of the reactive oligomer include an oligomer having any combination selected from a (meth)acrylate group, an epoxy group, a urethane bond, and an ester bond in the same molecule, such as a urethane acrylate having a (meth)acrylate group and a urethane bond in the same molecule, a polyester acrylate having a (meth)acrylate group and an ester bond in the same molecule, and an epoxy acrylate derived from an epoxy resin having an epoxy group and a (meth)acrylate group in the same molecule.
[0138] (Elastomer) Examples of elastomers (i.e. rubber) include natural rubber (NR), butadiene rubber (BR), styrene-butadiene copolymer rubber (SBR), isoprene rubber (IR), butyl rubber (IIR), acrylonitrile-butadiene rubber (NBR), acrylonitrile-styrene-butadiene copolymer rubber, chloroprene rubber, styrene-isoprene copolymer rubber, styrene-isoprene-butadiene copolymer rubber, isoprene-butadiene copolymer rubber, chlorosulfonated polyethylene rubber, modified natural rubber (epoxidized natural rubber (ENR), hydrogenated natural rubber, deproteinized natural rubber, etc.), ethylene-propylene copolymer rubber, acrylic rubber, epichlorohydrin rubber, polysulfide rubber, silicone rubber, fluororubber, urethane rubber, and the like.
[0139] When the resin is a thermoplastic resin, the cellulose fiber (which may be in the form of a dry powder according to the present disclosure, or a redispersion obtained by dispersing the cellulose fiber in a dispersion medium) can be melt-kneaded with the thermoplastic resin to produce a resin composite. - A method in which a resin monomer is mixed with cellulose fibers, a polymerization reaction is carried out, the resulting resin composite is extruded into a strand shape, and cooled and solidified in a water bath to obtain a pellet-shaped molded product; A method in which a mixture of resin and cellulose fibers is melt-kneaded using a single-screw or twin-screw extruder, extruded into a strand shape, and cooled and solidified in a water bath to obtain a pellet-shaped molded product; - A method in which a mixture of resin and cellulose fibers is melt-kneaded using a single-screw or twin-screw extruder, extruded into a rod or tube, and cooled to obtain an extrusion molded product; - A method of melt-kneading a mixture of resin and cellulose fiber using a single-screw or twin-screw extruder, and extruding the mixture through a T-die to obtain a sheet or film-like molded product; In a preferred embodiment, a mixture of resin and cellulose fibers is melt-kneaded using a single-screw or twin-screw extruder, extruded into a strand shape, and cooled and solidified in a water bath to obtain a pellet-shaped molded product. A specific example of a method for melt-kneading a resin and cellulose fibers is a method in which a resin and cellulose fibers transported in a desired ratio are mixed and then melt-kneaded. When the resin is a thermoplastic resin, the minimum processing temperatures recommended by thermoplastic resin suppliers are 255 to 270°C for nylon 66, 225 to 240°C for nylon 6, 170 to 190°C for polyacetal resin, and 160 to 180°C for polypropylene. The heating temperature setting is preferably in the range of 20°C higher than these recommended minimum processing temperatures. By setting the mixing temperature within this temperature range, the cellulose fibers and the resin can be mixed uniformly.
[0140] Resin composites containing a thermoplastic resin as a resin can be provided in various shapes. Specifically, resin pellets, sheets, fibers, plates, rods, etc. can be mentioned, but the resin pellet shape is more preferable from the viewpoint of ease of post-processing and ease of transportation. In this case, preferred pellet shapes include round, elliptical, cylindrical, etc., which differ depending on the cutting method used during extrusion processing. Pellets cut by a cutting method called underwater cutting are often round, pellets cut by a cutting method called hot cutting are often round or elliptical, and pellets cut by a cutting method called strand cutting are often cylindrical. In the case of round pellets, the preferred size is 1 mm or more and 3 mm or less in terms of pellet diameter. In the case of cylindrical pellets, the preferred diameter is 1 mm or more and 3 mm or less, and the preferred length is 2 mm or more and 10 mm or less. It is desirable to set the above diameter and length to be equal to or greater than the lower limit from the viewpoint of operational stability during extrusion, and it is desirable to set them to be equal to or less than the upper limit from the viewpoint of bite into the molding machine during post-processing.
[0141] A resin composite containing a thermoplastic resin as a resin can be used as various resin molded products. There is no particular limitation on the manufacturing method of the resin molded product, and any manufacturing method may be used, but injection molding, extrusion molding, blow molding, inflation molding, foam molding, etc. can be used. Among these, injection molding is most preferable from the viewpoint of design and cost.
[0142] When the resin is a thermosetting resin or a photocurable resin, the resin composite can be produced by, for example, a method of thoroughly dispersing cellulose fibers in a resin solution or resin powder dispersion and drying, a method of thoroughly dispersing cellulose fibers in a resin monomer liquid and polymerizing with heat, UV irradiation, a polymerization initiator, etc., a method of thoroughly impregnating a dry cellulose fiber powder with a resin solution or resin powder dispersion and drying, a method of thoroughly impregnating a dry cellulose fiber powder with a resin monomer liquid and polymerizing with heat, UV irradiation, a polymerization initiator, etc. When curing, various polymerization initiators, curing agents, curing accelerators, polymerization inhibitors, etc. can be blended.
[0143] When the resin is a thermosetting resin or a photocurable resin, a method may be used in which an uncured or semi-cured sheet called a prepreg is prepared, the prepreg is made into a single layer or a laminate, and the resin is cured and molded by applying pressure and heat. Examples of the method of applying pressure and heat include a press molding method, an autoclave molding method, a bagging molding method, a wrapping tape method, and an internal pressure molding method.
[0144] When the resin is a photocurable resin, the resin molded article can be produced by using various curing methods using active energy rays.
[0145] When the resin is an elastomer, the resin composite can be produced by a method of kneading dry powder of cellulose fiber with raw rubber in a dry state, or a method of dispersing or dissolving cellulose fiber and raw rubber in a dispersion medium, then drying and mixing. As a mixing method, a mixing method using a homogenizer is preferable because it can apply high shear force and pressure to promote dispersion, but other methods such as a propeller type stirring device, a rotary stirring device, an electromagnetic stirring device, and manual stirring can also be used. The resin composite containing the elastomer can be molded using a desired molding method such as mold molding, injection molding, extrusion molding, hollow molding, and foam molding to obtain an unvulcanized molded body of a desired shape such as a sheet, pellet, or powder. The unvulcanized molded body can be vulcanized by heat treatment or the like as necessary to obtain a resin molded body.
[0146] The resin molded product containing a thermoplastic resin or an elastomer may be partially (e.g., several portions) melted by heat treatment and then bonded to, for example, a resin or metal substrate. The resin molded product may be a coating applied to a resin or metal substrate, or may form a laminate with the substrate. The sheet-, film-, or fiber-shaped resin molded product may be subjected to secondary processing such as annealing, etching, corona treatment, plasma treatment, grain transfer, cutting, and surface polishing.
[0147] In the resin composite, the amount of cellulose fiber per 100 parts by mass of resin may be, from the viewpoint of the balance between processability and mechanical properties, preferably 0.001 part by mass or more, or 0.01 part by mass or more, or 0.1 part by mass or more, or 1 part by mass or more, and may be preferably 100 parts by mass or less, or 80 parts by mass or less, or 70 parts by mass or less, or 50 parts by mass or less. EXAMPLES
[0148] The present invention will be further described with reference to examples, but the present invention is not limited to these examples.
[0149] <Production of cellulose fiber wet cake> <Cellulose fiber 1> Celish KY-100G (solid content concentration: 10% by mass) manufactured by Daicel FineChem Ltd. was used as is.
[0150] <Cellulose fiber 2> Cotton linter pulp was cut and then washed with water to remove impurities, and the purified pulp was added to pure water so that the solid content was 1.5% by mass, and then highly shortened and fibrillated by beating to obtain defibrated cellulose. Here, the beating was performed using a disc refiner, with the pulp treated for 2.5 hours with a beating blade with high cutting function, and then beaten for an additional 2 hours with a beating blade with high defibrating function, and the slurry was filtered and concentrated to use the obtained cellulose fiber (solid content concentration 20% by mass).
[0151] <Cellulose fiber 3> 1 kg of linter pulp and 19 kg of DMSO were charged into a KAPPA VITA (registered trademark) homomixer (tank size 35 L) manufactured by NETZSCH Vakumix, and defibrated for 8 hours at a homomixer rotation speed of 6000 rpm (circumferential speed 29 m / s). Then, 0.321 kg of sodium bicarbonate and 2.1 kg of vinyl acetate were added and acetylation was carried out for 4 hours at 60°C. During acetylation, in order to prevent retention in the circulation line, the homomixer rotation speed was set to 2500 rpm (circumferential speed 12 m / s), just before the shear force rises. The reaction mixture was washed with water, filtered and concentrated, and the resulting acetylated cellulose fiber having a degree of substitution of 1.0 (solid content concentration: 15% by mass) was used.
[0152] <Production of dry powder of cellulose fiber> [Example 1] The cellulose fiber wet cake prepared above was used to produce a dry powder according to the following procedure. Equipment: High-speed mixer manufactured by EarthTechnica Corporation (model number: FS10) Raw material: cellulose fiber 1 (5 kg) Conditions: Jacket temperature 70°C, agitation with an agitator (circumferential speed 2 m / s) and chopper (rotation speed 3500 rpm) while reducing the pressure to -70 kPa with a vacuum pump. t-Butanol (1 kg) was added at the stage where reduced pressure drying was performed until the moisture content reached 50% by mass, and reduced pressure drying was performed until the product temperature reached 60°C and the moisture content was less than 5% by mass.
[0153] [Example 2] The cellulose fiber wet cake prepared above was used to produce a dry powder according to the following procedure. Equipment: High-speed mixer manufactured by EarthTechnica Corporation (model number: FS10) Raw materials: Cellulose fiber 1 (5 kg) + Sannix GL-3000 (214 g) manufactured by Sanyo Chemical Industries, Ltd. Conditions: Jacket temperature 70°C, stirring with an agitator (circumferential speed 1 m / s) and chopper (rotation speed 3500 rpm), reducing the pressure to -70 kPa with a vacuum pump, and drying under reduced pressure was performed until the product temperature reached 60°C.
[0154] [Example 3] The cellulose fiber wet cake prepared above was used to produce a dry powder according to the following procedure. Equipment: Lödige Mixer (model number: M20) manufactured by Chuo Kiko Co., Ltd. Raw materials: Cellulose fiber 1 (5 kg) + Sannix GL-3000 (214 g) manufactured by Sanyo Chemical Industries, Ltd. Conditions: Jacket temperature 100°C, stirring with an agitator (circumferential speed 4 m / s) and chopper (rotation speed 5000 rpm), reducing the pressure to -90 kPa with a vacuum pump, and drying under reduced pressure was performed until the product temperature reached 90°C.
[0155] [Example 4] The cellulose fibers 2 (2.5 kg) were used instead of the cellulose fibers 1, and vacuum drying was carried out in the same manner as in Example 2.
[0156] [Example 5] The cellulose fibers were dried under reduced pressure in the same manner as in Example 1, except that the cellulose fibers 3 (3.3 kg) were used instead of the cellulose fibers 1.
[0157] [Example 6] The cellulose fibers were dried under reduced pressure in the same manner as in Example 2, except that the cellulose fibers 3 (3.3 kg) were used instead of the cellulose fibers 1.
[0158] [Example 7] The cellulose fiber wet cake prepared above was used to produce a dry powder according to the following procedure. Equipment: High-speed mixer manufactured by EarthTechnica Corporation (model number: FS10) Raw materials: Cellulose fiber 3 (3.3 kg) + 5% by weight acetone solution of Eastman Chemical Company CAB381-20 (214 g) Conditions: Jacket temperature 70°C, agitation with an agitator (circumferential speed 1 m / s) and chopper (3500 rpm) while reducing the pressure to -70 kPa with a vacuum pump. Acetone (1 kg) was added at the stage where reduced pressure drying was performed until the moisture content reached 50 mass%, and reduced pressure drying was performed until the product temperature reached 60°C and the residual solvent content was less than 3 mass%.
[0159] [Example 8] The mixture was dried under reduced pressure in the same manner as in Example 2, except that the peripheral speed of the agitator was set to 15 m / s.
[0160] [Example 9] The mixture was dried under reduced pressure in the same manner as in Example 2, except that the peripheral speed of the agitator was set to 0.5 m / s.
[0161] [Example 10] Drying under reduced pressure was carried out in the same manner as in Example 3, except that the peripheral speed of the agitator was set to 1 m / s and the rotation speed of the chopper was set to 6000 rpm.
[0162] [Example 11] Drying under reduced pressure was carried out in the same manner as in Example 2, except that the rotation speed of the chopper was set to 200 rpm.
[0163] [Example 12] The cellulose fiber wet cake prepared above was used to produce a dry powder according to the following procedure. Equipment: High-speed mixer manufactured by EarthTechnica Corporation (model number: FS10) Raw material: cellulose fiber 3 (3.3 kg) Conditions: Jacket temperature 70°C, agitation with an agitator (circumferential speed 2 m / s) and chopper (3500 rpm) was performed while reducing the pressure to -70 kPa with a vacuum pump. t-butanol (1 kg) was added as the first additional medium when the moisture content was 50 mass%, and drying under reduced pressure was continued. t-butanol (1 kg) was added as the second additional medium when the moisture content was 20 mass%, and drying under reduced pressure was performed until the product temperature reached 60°C and the residual solvent content was less than 3 mass%.
[0164] [Example 13] The cellulose fiber wet cake prepared above was used to produce a dry powder according to the following procedure. Equipment: High-speed mixer manufactured by EarthTechnica Corporation (model number: FS10) Raw material: cellulose fiber 3 (3.3 kg) Conditions: Jacket temperature 70°C, agitation with an agitator (circumferential speed 2 m / s) and chopper (3500 rpm) was performed while reducing the pressure to -70 kPa with a vacuum pump. 1-Methoxy-2-propanol (1 kg) was added as the first additional medium when the moisture content was 50 mass%, and drying under reduced pressure was continued. t-Butanol (1 kg) was added as the second additional medium when the moisture content was 10 mass%, and drying under reduced pressure was performed until the product temperature reached 60°C and the residual solvent content was less than 3 mass%.
[0165] [Example 14] The cellulose fiber wet cake prepared above was used to produce a dry powder according to the following procedure. Equipment: High-speed mixer manufactured by EarthTechnica Corporation (model number: FS10) Raw material: cellulose fiber 3 (3.3 kg) Conditions: Jacket temperature 100°C, agitation with an agitator (circumferential speed 2m / s) and chopper (3500rpm) were used to reduce the pressure to -70kPa with a vacuum pump. At the stage where reduced pressure drying was performed until the moisture content reached 75% by mass, 2.0kg of i-butanol was added dropwise as an additional medium over 30 minutes. During this time, reduced pressure drying continued, and the total liquid content (the total liquid content of both water and i-butanol measured with a heat drying type moisture content meter) at the end of the drop was 72% by mass. In addition, the mass ratio of water:i-butanol at the end of the drop was calculated using gas chromatography to be 67:33. Reduced pressure drying was continued even after the drop was completed, and was performed until the product temperature finally reached 70°C and the residual solvent content was less than 3% by mass.
[0166] [Example 15] Except for changing the amount of i-butanol dropped to 3.0 kg and the dropping time to 45 minutes, drying under reduced pressure was carried out in the same manner as in Example 14. At the end of the dropping, the total liquid ratio was 74 mass%, and the mass ratio of water:i-butanol was 31:69.
[0167] [Example 16] Except for changing the amount of i-butanol dropped to 4.0 kg and the dropping time to 60 minutes, drying under reduced pressure was carried out in the same manner as in Example 14. At the end of the dropping, the total liquid ratio was 73 mass%, and the mass ratio of water:i-butanol was 4:96.
[0168] [Example 17] The cellulose fiber wet cake prepared above was used to produce a dry powder according to the following procedure. Equipment: Nippon Coke & Engineering Co., Ltd. Henschel mixer (model: FM20) Raw material: cellulose fiber 1 (5 kg) Conditions: Jacket temperature 70°C, stirring with an agitator (circumferential speed 8 m / s) and chopper (circumferential speed 8 m / s), pressure reduced to -70 kPa with a vacuum pump. Drying under reduced pressure was continued until the moisture content reached 50% by mass, at which point t-butanol (1 kg) was added, and drying under reduced pressure was continued until the product temperature reached 60°C and the moisture content was less than 5% by mass.
[0169] [Comparative Example 1] The cellulose fiber wet cake prepared above was used to produce a dry powder according to the following procedure. Equipment: Primix Hi-Vismix (Model: 2P-1) Raw materials: Cellulose fiber 1 (0.3 kg) + Sannix GL-3000 (13 g) manufactured by Sanyo Chemical Industries, Ltd. Conditions: jacket temperature 70°C, stirring with two blades (planetary rotation at 50 rpm), reducing the pressure to -95 kPa with a vacuum pump, and drying under reduced pressure was performed until the residual moisture content reached less than 5% by mass.
[0170] [Comparative Example 2] Except for stopping the agitator and only performing chopper stirring, drying under reduced pressure was performed in the same manner as in Example 1. Most of the cellulose fibers were dried without coming into contact with the chopper, making it difficult to redisperse them and measure their viscosity using the method described below.
[0171] [Comparative Example 3] The cellulose fiber wet cake prepared above was used to produce a dry powder according to the following procedure. Equipment: Espec Corporation thermostat (model number: SPH-201) Raw material: cellulose fiber 1 (0.3 kg) Conditions: The mixture was heated at 105° C. without stirring at normal pressure, and dried until the residual moisture content reached less than 5% by mass. The cellulose fibers aggregated and dried, making it difficult to redisperse and measure viscosity using the method described below.
[0172] <Production of resin composite> The dry powder of cellulose fibers produced above and a thermoplastic resin (UBE Nylon 1013B manufactured by Ube Industries, Ltd.) were mixed in such a ratio that the cellulose fibers accounted for 10 mass% of the resin composite, and a resin composite was produced according to the following procedure. Using a small kneader (manufactured by Xplore instruments, product name "Xplore"), the material was circulated and kneaded for 5 minutes at 260°C, 200 rpm (shear rate 1570 (1 / s)) to confirm the torque. The better the dispersion of the cellulose fiber in the thermoplastic resin, the higher the melt viscosity. The molten resin was then directly transferred to an attached injection molding machine to prepare dumbbell-shaped test pieces according to the ISO037-3 standard, which were used for evaluation.
[0173] [Comparative Example 4] The torque was observed when only a thermoplastic resin (UBE nylon 1013B manufactured by Ube Industries, Ltd.) was kneaded without using the dry cellulose fiber powder.
[0174] Evaluation <Evaluation of cellulose fibers> [Preparation of porous sheet] First, the wet cake was added to t-butanol, and further dispersed in a mixer or the like until no aggregates were formed. The concentration was adjusted to 0.5% by mass per 0.5 g of cellulose fiber solids. 100 g of the resulting t-butanol dispersion was filtered on filter paper, dried at 150°C, and the filter paper was peeled off to obtain a sheet. The air resistance of this sheet was 10 g / m2. 2 The porous sheets with a permeability of 100 sec / 100 ml or less were used as measurement samples. The basis weight W (g / m2) of the sample left standing for one day in an environment of 23°C and 50% RH 2 After measuring the air permeability, the air permeability resistance R (sec / 100ml) was measured using an Oken air permeability tester (manufactured by Asahi Seiko Co., Ltd., model EG01). 2 The value per unit area was calculated. Weight 10g / m 2 Air resistance per unit (sec / 100ml) = R / W x 10
[0175] [Acyl Substitution Degree (DS)] The infrared spectrum of the porous sheet at five points was measured by the ATR-IR method using a Fourier transform infrared spectrophotometer (FT / IR-6200 manufactured by JASCO Co., Ltd.) The infrared spectrum measurement was performed under the following conditions. Number of times accumulated: 64 times, Wavenumber resolution: 4cm -1 , Measurement wave number range: 4000~600cm -1 , ATR crystal: Diamond, Incident angle: 45° From the obtained IR spectrum, the IR index was calculated according to the following formula (1): IR index = H1730 / H1030 (1) In the formula, H1730 and H1030 are at 1730 cm -1 , 1030cm -1 (absorption band of CO stretching vibration of cellulose backbone chain) -1 and 1500cm -1 The line connecting the -1 and 1500cm -1 The line connecting these points is taken as the baseline, and the absorbance is calculated when this baseline is taken as 0. Then, the average degree of substitution at each measurement site was calculated from the IR index according to the following formula (2), and the average value was taken as DS. DS = 4.13 × IR index (2)
[0176] [DS heterogeneity ratio (CV)] The porous sheet that had been subjected to the ATR-IR measurement was frozen and crushed to prepare powder samples of cellulose fiber. The powder was placed on 10 2.5 mm diameter dish-shaped sample stands, the surfaces were pressed down to make them flat, and XPS measurements were performed on each. Peak separation was performed on the obtained C1s spectrum, and the DSs of each sample was calculated using the area intensity (Ixf) of the peak (286 eV) derived from the OC=O bond of the acetyl group relative to the area intensity (Ixp) of the peak (289 eV, CC bond) attributed to carbons C2-C6 derived from the pyranose ring of cellulose, and the average was taken as the DSs of the cellulose fiber. DSs = (Ixf) x 5 / (Ixp)
[0177] The conditions used for the XPS measurement are as follows: Equipment used: ULVAC-Phi VersaProbe II Excitation source: mono.AlKα 15kV×3.33mA Analysis size: Approx. 200 μm φ Photoelectron extraction angle: 45° Capture Area Narrow scan: C 1s, O 1s Pass Energy: 23.5eV
[0178] Based on the above DS and DSs, the DS heterogeneity ratio (CV) was calculated according to the following formula. DS heterogeneity ratio (CV) = DSs / DS
[0179] [Average fiber diameter equivalent to specific surface area] Approximately 0.2 g of the porous sheet sample was dried under vacuum at 150°C for 2 hours using a surface area and pore size distribution analyzer (Nova-4200e, manufactured by Quantachrome Instruments). The amount of nitrogen gas adsorbed at the boiling point of liquid nitrogen was then measured at five points (multipoint method) in the range of relative vapor pressure (P / P0) between 0.05 and 0.2. The BET surface area (m 2 The average fiber diameter equivalent to the specific surface area was calculated from the specific surface area using the following formula, and this was taken as the average fiber diameter D of cellulose. D(nm)=2667 / specific surface area(m 2 / g)
[0180] [Average fiber diameter based on electron microscope images] The wet cake was diluted to 0.01% by mass with t-butanol, dispersed using a high-shear homogenizer (IKA, product name "Ultra Turrax T18") at a rotation speed of 15,000 rpm for 3 minutes, cast onto an osmium-deposited silicon substrate, air-dried, and measured with a high-resolution scanning electron microscope (Hitachi High-Tech, Regulus 8220). The measurement was performed by adjusting the magnification so that at least 100 cellulose fibers were observed, and the minor diameter (D) of 100 randomly selected cellulose fibers was measured, and the arithmetic average of the 100 cellulose fibers was calculated.
[0181] [Weight average molecular weight (Mw), number average molecular weight (Mn) and Mw / Mn ratio] 0.88 g of the porous sheet was weighed, cut into small pieces with scissors, lightly stirred, 20 mL of pure water was added, and left for one day. Next, the water and solids were separated by centrifugation. Next, 20 mL of acetone was added, lightly stirred, and left for one day. Next, the acetone and solids were separated by centrifugation. Next, 20 mL of N,N-dimethylacetamide was added, lightly stirred, and left for one day. N,N-dimethylacetamide and solids were separated again by centrifugation, and then 20 mL of N,N-dimethylacetamide was added, lightly stirred, and left for one day. N,N-dimethylacetamide and solids were separated by centrifugation, and 19.2 g of N,N-dimethylacetamide solution prepared so that lithium chloride was 8 mass percent was added to the solids, and the mixture was stirred with a stirrer and visually confirmed to be dissolved. The solution in which cellulose was dissolved was filtered through a 0.45 μm filter, and the filtrate was used as a sample for gel permeation chromatography. The apparatus and measurement conditions used are as follows. Equipment: Tosoh HLC-8120 Column: TSKgel SuperAWM-H (6.0mm I.D. x 15cm) x 2 Detector: RI detector Eluent: N,N-dimethylacetamide (lithium chloride 0.2%) Flow rate: 0.6mL / min Calibration curve: Pullulan conversion
[0182] [Average content of alkali-soluble polysaccharides] The alkali-soluble polysaccharide content was calculated by subtracting the α-cellulose content from the holocellulose content (Wise method) according to the method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pp. 92-97, 2000) for cellulose fibers. The alkali-soluble polysaccharide content was calculated three times for each sample, and the number average of the calculated alkali-soluble polysaccharide contents was taken as the average alkali-soluble polysaccharide content of the cellulose fibers.
[0183] [Average content of acid-insoluble components] The amount of acid-insoluble components was determined by the Clason method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000) for cellulose fibers. The completely dried cellulose fibers were precisely weighed, placed in a designated container, and 72% by mass of concentrated sulfuric acid was added. The contents were appropriately pressed with a glass rod so as to be uniform, and then autoclaved to dissolve the cellulose and hemicellulose in the acid solution. After cooling, the contents were filtered with glass fiber filter paper, and the acid-insoluble components were obtained as residue. The acid-insoluble component content was calculated from the weight of the acid-insoluble components, and the number average of the acid-insoluble component contents calculated for the three samples was taken as the average acid-insoluble component content.
[0184] [Thermal decomposition onset temperature (T D )] The thermal analysis of the porous sheet was evaluated by the following measurement method. Equipment: Rigaku Thermo plus EVO2 Sample: 10 mg of circular samples were cut out from the porous sheet and placed in an aluminum sample pan. Sample size: 10mg Measurement conditions: In a nitrogen flow of 100 ml / min, the temperature was increased from room temperature to 150°C at a rate of 10°C / min, and after holding at 150°C for 1 hour, it was cooled to 30°C. Next, the temperature was increased from 30°C to 450°C at a rate of 10°C / min. T D Calculation method: Calculated from a graph with temperature on the horizontal axis and weight remaining rate % on the vertical axis. Starting from the weight (weight loss 0 wt%) of the porous sheet at 150°C (state where moisture is almost completely removed), the temperature was further increased, and a straight line was obtained that passed through the temperatures at 1 wt% weight loss and 2 wt% weight loss. The temperature at the point where this straight line intersects with the horizontal line (baseline) that passes through the starting point of 0 wt% weight loss was determined as the thermal decomposition onset temperature (T D ) was decided.
[0185] [1wt% weight loss temperature] 1wt% weight loss temperature calculation method: T D The temperature at which the weight loss reached 1 wt% was calculated was taken as the 1 wt% weight loss temperature.
[0186] [250℃ weight loss rate] Equipment: Rigaku Thermo plus EVO2 Sample: 10 mg of circular samples were cut out from the porous sheet and placed in an aluminum sample pan. Sample size: 10mg Measurement conditions: In a nitrogen flow of 100 ml / min, the temperature was increased from room temperature to 150°C at a rate of 10°C / min, and then held at 150°C for 1 hour.The temperature was then increased from 150°C to 250°C at a rate of 10°C / min, and then held at 250°C for 2 hours. Calculation method for the rate of weight change at 250°C: Taking W0, the weight at the time when 250°C was reached, as the starting point, and W1, the weight after maintaining at 250°C for 2 hours, was used to calculate the rate of weight change at 250°C using the following formula. Weight change rate at 250℃ (%): (W1-W0) / W0×100
[0187] <Bulk density of dry cellulose fiber powder> The dry cellulose fiber powder was poured into a 100 mL stainless steel cylindrical container until it overflowed, and the dry powder was then leveled off and the weight was measured to calculate the content.
[0188] <Viscosity of cellulose fiber slurry and redispersion> The sample solution prepared by dispersing cellulose fibers before drying or dry powder with a homogenizer to form a 0.5% by mass aqueous dispersion was subjected to viscosity measurement using a coaxial cylinder configuration with a Thermo Fisher Scientific rheometer, HAAKE MARS. When reading the viscosity at a shear rate of 100 s -1 −1, in order to suppress the variation in data, the viscosity at a shear rate of 100 s -1 −1 was read after applying a certain shear history. Specifically, after putting the 0.5% by mass sample solution into the coaxial cylinder cup, the shear rate was increased from 1 s -1 −1 to 100 s -1 −1 over 100 seconds using the rheometer, and then the shear rate was decreased from 100 s -1 −1 to 1 s -1 −1 over 100 seconds, and then the shear rate was increased again from 1 s -1 −1 to 100 s -1 −1 over 100 seconds, and the viscosity at the time when 100 s -1 −1 was reached was read.
[0189] <Water content and total liquid ratio of CNF slurry and dry powder> A heating drying type moisture meter (manufactured by A&D Company, MX-50) was used. 5 g of the slurry and dry powder were placed in an aluminum dish, heated at 150 °C, and the moisture content was measured. When the slurry contained a volatile organic solvent, the total liquid ratio was measured as the sum of water and the organic solvent.
[0190] <Water:i-butanol ratio of CNF slurry> The CNF slurry was diluted with dimethylformamide (DMF) to 0.1% by mass to prepare a DMF solution, and the solids were removed with a 0.2 μm syringe filter. The obtained DMF solution was measured by gas chromatography. The i-butanol mass% in the DMF solution was calculated from the peak area of the obtained chromatogram, and then the i-butanol mass% in each CNF slurry was calculated from the dilution ratio of the CNF slurry. In addition, when calculating the i-butanol mass% from the peak area, a calibration curve was created in advance using DMF standard solutions containing different concentrations of i-butanol (i-butanol concentrations were 50 ppm by mass, 100 ppm by mass, and 500 ppm by mass). Finally, the total liquid ratio (the sum of both water and i-butanol) of the CNF slurry was measured with a heat-drying type moisture content meter, and the water:i-butanol ratio was calculated from the following formula. Water:i-butanol = (total liquid percentage (mass%)) - (mass% of i-butanol):mass% of i-butanol Gas chromatography measurements were carried out under the following conditions. Equipment: Shimadzu Corporation GC-2010 Column: DB-WAX (30m x 0.25mm, film thickness 0.25μm) Column temperature: 40°C → 15°C / min to 100°C → 20°C / min to 200°C Column flow rate: 1.0 ml / min Inlet temperature: 200℃ Injection method: Split method (1:50) Detector temperature: 230℃ Injection volume: 1μl
[0191] <Tensile strength and elongation at break of resin composite> The obtained test pieces were measured for tensile strength at yield and elongation at break according to ISO 527-1. For the molded pieces that broke before yielding, the maximum strength was used instead.
[0192] [Table 1]
[0193] [Table 2] [Industrial Applicability]
[0194] According to the present invention, a dry powder of cellulose fibers can be produced which is provided as a dry powder exhibiting good redispersibility, and which is therefore inexpensive to store and transport, and which is extremely useful as a property improver for resin composites.
Claims
1. 1. A method for producing a dry powder of cellulose fibers, comprising the steps of: A slurry preparation step of preparing a slurry containing cellulose fibers and water; and a granulation step of agitating the slurry under reduced pressure to form a dry powder of the cellulose fibers; Including, The number average fiber diameter of the cellulose fibers is 10 nm or more and 1000 nm or less, The method, wherein the granulating step comprises forming particles of the cellulose fibers by the agitation and chopping the particles.
2. 10. The method of claim 1, wherein the slurry contains 5% or more by weight water at the start of the granulation step.
3. 3. The method of claim 1 or 2, wherein an additional medium, which is a liquid medium other than water, is added to the slurry in the granulation step.
4. 4. The method of claim 3, wherein an additional medium, which is a liquid medium other than water, is added to the slurry in two or more portions during the granulation step.
5. The method according to claim 3 or 4, wherein the additional medium is selected from the group consisting of: alcohols having a boiling point of 50° C. to 170° C.; ethers; carboxylic acids; esters; ketones; and nitrogen-containing solvents.
6. The method according to any one of claims 3 to 5, wherein the additional medium is a substance which forms an azeotrope with water.
7. 7. The method of claim 6, wherein the additional medium is added to the slurry in a proportion greater than the azeotropic composition with water.
8. The method according to any one of claims 3 to 7, wherein the additional medium is added to the slurry in a mass ratio of water:additional medium in the slurry ranging from 1:99 to 90:
10.
9. 1. A method for producing a dry powder of cellulose fibers, comprising the steps of: A slurry preparation step of preparing a slurry comprising cellulose fibers and a liquid medium; and a granulation step of agitating the slurry under reduced pressure to form a dry powder of the cellulose fibers; Including, The number average fiber diameter of the cellulose fibers is 10 nm or more and 1000 nm or less, The method, wherein the granulating step comprises forming particles of the cellulose fibers by the agitation and chopping the particles.
10. 10. The method of claim 9, wherein the liquid medium is at least one selected from the group consisting of alcohols having a boiling point of 50° C. to 170° C.; ethers; carboxylic acids; esters; ketones; and nitrogen-containing solvents.
11. The method according to any one of claims 1 to 10, wherein a binder is added to the slurry in the slurry preparation step and / or the granulation step.
12. The method of claim 11 , wherein the binder is selected from the group consisting of polyalkylene oxides, cellulose ethers, and cellulose esters.
13. The method according to claim 11 or 12, wherein the binder is dissolved in a medium and added to the slurry in the slurry preparation step and / or the granulation step.
14. The granulation step is carried out in a granulator equipped with an agitator blade, a chopper blade, and a pressure reducing mechanism, In the granulation step, the stirring is performed by rotating the stirring blade at a peripheral speed of 0.5 m / sec to 40 m / sec, and the chopper pulverization is performed by rotating the chopper blade at a speed of 100 rpm to 6000 rpm; The method according to any one of claims 1 to 13, wherein the granulator is configured such that the chopper-milled particles are further subjected to said agitation.
15. The granulation step is carried out in a granulator equipped with an agitator blade, a chopper blade, and a pressure reducing mechanism, In the granulation step, the stirring is performed by rotating the stirring blade at a peripheral speed of 0.5 m / sec to 40 m / sec, and the chopper pulverization is performed by rotating the chopper blade at a peripheral speed of 0.5 m / sec to 40 m / sec, The method according to any one of claims 1 to 14, wherein the granulator is configured such that the chopper-milled particles are further subjected to said agitation.
16. 16. The method of claim 15, wherein the peripheral speed of the chopper blade is less than or equal to the peripheral speed of the agitator blade.
17. The method according to any one of claims 1 to 16, wherein the granulation step is carried out at a temperature of 20 to 160°C and a reduced pressure of -100 kPa to -1 kPa.
18. 18. The method of any one of claims 1 to 17, wherein the bulk density of the dry powder is from 0.05 g / mL to 1.0 g / mL.
19. The method according to any one of the preceding claims, wherein cellulose fibres derived from cotton linters are used.
20. The method according to any one of claims 1 to 19, wherein chemically modified cellulose fibres are used.
21. The method according to any one of claims 1 to 20, wherein cellulose fibres are used which are chemically modified with hydrophobic substituents.
22. 22. A method for producing a composite comprising cellulose fibers and a resin, the method comprising preparing a dry powder by the method according to any one of claims 1 to 21, and mixing the dry powder with the resin.
23. The resin is a thermoplastic resin, 23. The method of claim 22, wherein the dry powder and the resin are mixed by melt kneading.
Citation Information
Patent Citations
Fiber assembly of microfiber-shaped cellulose and method for producing the same
JP2009203559A
Microfiber and method for producing the same
JP2012224960A
Method for producing cationized hydroxyalkyl cellulose
JP2015067820A
Methods, systems, and apparatus for processing fibrilcellulose and fibrilcellulose materials.
JP2015512964A
Powdery cellulose nanofibers for the production of compositions, method for producing the same, and compositions
JP2017210596A